Salts of nitrogen-containing heterocyclic compounds, solid forms of the salts, pharmaceutical compositions and uses thereof
By developing salt forms and solid forms of nitrogen heterocyclic compounds, the problems of existing ATX inhibitors in drug formation and stability have been solved, and better biological activity and clinical application effects have been achieved.
Patent Information
- Application Number
- JP2023526687
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-07-28
- Filing Date
- 2021-07-28
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2041-07-28
AI Technical Summary
Existing ATX inhibitors have drug formation and stability problems in the treatment of diseases associated with high LPA levels, which affects their clinical application.
Nitrogen-containing heterocyclic compounds and their salts in salt form and solid form are developed, including chlorides, sulfates, phosphates, hydroxylates, etc., and crystalline forms or non-morphology with good biological activity are prepared through different acidification reactions and crystallization processes.
The forms and solid forms of these salts improve the solubility, stability and hygroscopicity of the drug, provide a better foundation for drug development, and significantly improve the effectiveness of clinical applications.
Smart Images

Figure 0007663685000052 
Figure 0007663685000053 
Figure 0007663685000054
Abstract
Description
[Technical field]
[0001] This application claims priority from the applicant's prior application, bearing application number 202010727300.5 and title "Salts of nitrogen-containing heterocyclic compounds and solid forms, pharmaceutical compositions and uses thereof," filed with the State Intellectual Property Office of the People's Republic of China on July 28, 2020, the entire contents of which are incorporated herein by reference.
[0002] The present invention belongs to the field of medicinal chemistry, and specifically relates to salts of nitrogen-containing heterocyclic compounds and solid forms, pharmaceutical compositions and uses of the salts. [Background technology]
[0003] Autotaxin (ATX) is a secreted glycoprotein with phosphodiesterase (PDE) activity and is a member of the extracellular pyrophosphatase / phosphodiesterase (ENPP) family, hence also called ENPP2. ATX also has lysophospholipase D (LysoPLD) activity and can hydrolyze lysophosphatidylcholine (LPC) to lysophosphatidic acid (LPA), which has biological activity. LPA is an intracellular lipid medium that affects many biological and biochemical processes. Studies have shown that inhibiting ATX under pathological conditions reduces LPA levels and therefore provides therapeutic benefit to unmet clinical needs including cancer, lymphocyte homing, chronic inflammation, neuropathic pain, fibrosis, thrombosis, cholestatic pruritus, or fibrotic diseases induced, mediated, and / or propagated by elevated LPA levels and / or ATX activation. Currently, ATX inhibitors have been found to be useful in the treatment of diseases associated with elevated LPA levels, including cancer, lymphocyte homing, chronic inflammation, neuropathic pain, fibrosis, thrombosis, cholestatic pruritus, and fibrotic diseases such as idiopathic pulmonary fibrosis (IPF).
[0004] The Chinese Patent of Invention Application with application number 202010074393.6 describes a compound of formula (I) that has ATX inhibitory activity. [ka]
[0005] The chemical name of the compound of formula (I) is (R)-2-((1-(1H-1,2,3-triazol-5-yl)propan-2-yl)oxy)-1-(2-((2,3-dihydro-1H-inden-2-yl)amino)-5,7-dihydro-6H-pyrrolo[3,4-d]pyrimidin-6-yl)ethan-1-one. Based on the good biological activity of the compound, it is necessary to develop suitable salt forms and solid forms thereof to obtain improved drug formability or other properties. Summary of the Invention
[0006] To remedy the above technical problems, the present invention provides a salt of a compound of formula (I) or a solid form of the salt thereof: [ka]
[0007] The salts are selected from inorganic or organic acid salts, and the solid form may be crystalline or amorphous.
[0008] According to an embodiment of the present invention, the inorganic acid salt is a salt formed between the compound of formula (I) and an inorganic acid. Preferably, the inorganic acid is one or more selected from hydrochloric acid, sulfuric acid, phosphoric acid, and hydrobromic acid.
[0009] According to an embodiment of the present invention, the inorganic acid salt includes one or more salts selected from the salts of the compound of the following formula (I), such as hydrochloride, sulfate, phosphate, hydrobromide, etc., but is not limited thereto.
[0010] According to an embodiment of the present invention, the organic acid salt is a salt formed between the compound of formula (I) and an organic acid.Preferably, the organic acid is one or more selected from aspartic acid, maleic acid, glutamic acid, mucic acid, tartaric acid, fumaric acid, citric acid, glycolic acid, malic acid, hippuric acid, lactic acid, ascorbic acid, succinic acid, adipic acid, sebacic acid, lauric acid, p-toluenesulfonic acid, methanesulfonic acid, benzenesulfonic acid, benzoic acid, and niacin.
[0011] According to an embodiment of the present invention, the organic acid salt includes one or more salts selected from the group consisting of aspartate, maleate, glutamate, mucate, tartrate, fumarate, citrate, glycolate, malate, hippurate, lactate, ascorbate, succinate, adipate, sebacate, laurate, p-toluenesulfonate, methanesulfonate, benzenesulfonate, benzoate, and niacin salt, and is represented by the following formula (I):
[0012] According to an exemplary embodiment of the invention, the salt is selected from the hydrochloride, fumarate or benzenesulfonate salt of the compound of formula (I).
[0013] According to an embodiment of the present invention, in the above salt, the molar ratio of the compound of formula (I) to the acid (such as an inorganic acid or an organic acid) that forms the salt may be 1:(0.5 to 2), for example, 1:(0.5 to 1).
[0014] According to an embodiment of the present invention, the crystalline form may be a solid form selected from the salts of the compound of formula (I), such as hydrochloride (1:1), sulfate (1:1), maleate (1:1), phosphate (1:1), tartrate (1:1), fumarate (1:1), citrate (1:1), glycolate (1:0.5), succinate (1:(0.5-1)), adipate (1:1), sebacate (1:1), p-toluenesulfonate (1:1), benzenesulfonate (1:1) and hydrobromide (1:1), for example in crystalline or amorphous form. In which, the ratio indicated in parentheses after each salt is the molar ratio of the compound of formula (I) to the corresponding acid in that salt. In the context of the present invention, when referring to the above salts, they all have the molar ratios stated in parentheses.
[0015] According to an embodiment of the present invention, the crystalline form may be selected from crystalline forms of a salt of the compound of formula (I), such as hydrochloride crystalline form A, sulfate crystalline form A, maleate crystalline form A, phosphate crystalline form A, tartrate crystalline form A, tartrate crystalline form B, tartrate crystalline form C, fumarate crystalline form A, citrate crystalline form A, glycolate crystalline form A, succinate crystalline form A, succinate crystalline form B, adipate crystalline form B, sebacate crystalline form A, p-toluenesulfonate crystalline form A, benzenesulfonate crystalline form A, hydrobromide crystalline form A or hydrobromide crystalline form B, for example selected from hydrochloride crystalline form A, fumarate crystalline form A or benzenesulfonate crystalline form A of the compound of formula (I).
[0016] In the context of the present invention, unless otherwise stated, the margin of error for 2θ angle values in X-ray powder diffraction (XRPD) data is ±0.2°.
[0017] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the hydrochloride crystalline form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 7.48±0.20°, 13.13±0.20°, 16.47±0.20° and 23.94±0.20°.
[0018] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the hydrochloride crystalline form A has characteristic peaks at 2θ angles of 7.48±0.20°, 13.13±0.20°, 16.47±0.20°, 18.29±0.20°, 19.89±0.20° and 23.94±0.20°.
[0019] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the hydrochloride crystalline form A has characteristic peaks at 2θ angles of 7.48±0.20°, 13.13±0.20°, 14.86±0.20°, 16.47±0.20°, 18.29±0.20°, 19.89±0.20°, 23.94±0.20° and 26.92±0.20°.
[0020] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the above hydrochloride crystalline form A obtained using Cu-Kα radiation are shown in Table 1 below: [Table 1]
[0021] According to an embodiment of the present invention, the hydrochloride salt crystalline form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0022] According to an embodiment of the present invention, the hydrochloride crystalline form A has one, two, three or four of the following characteristics: (1) The TGA curve of the hydrochloride crystalline form A shows a weight loss of about 2.83% at 150.0±3°C; (2) The DSC curve of the hydrochloride crystalline form A has an endothermic peak onset at 163.5±3°C; (3) The DSC curve of the hydrochloride crystalline form A has an endothermic peak at 170.9±10°C, and in particular, the DSC curve of the hydrochloride crystalline form A has an endothermic peak at 170.9±5°C; (4) The DVS curve of the hydrochloride crystalline form A has a water adsorption of less than about 10%, for example less than about 5%, particularly less than about 3.85%, under conditions of 0% RH to 80% RH.
[0023] According to an embodiment of the present invention, the hydrochloride crystalline form A has one, two or three of the following characteristics: (1) Hydrochloride crystalline form A has a TGA curve essentially as shown in FIG. 20; (2) The hydrochloride salt crystalline form A has a DSC curve essentially as shown in FIG. 20; (3) The hydrochloride salt crystalline form A has a DVS curve essentially as shown in FIG.
[0024] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the Sulfate Crystalline Form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.49±0.20°, 15.88±0.20°, 17.48±0.20°, and 22.40±0.20°.
[0025] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the Sulfate Salt crystalline form A has characteristic peaks at 2θ angles of 5.49±0.20°, 6.93±0.20°, 11.08±0.20°, 15.88±0.20°, 17.48±0.20°, 20.82±0.20° and 22.40±0.20°.
[0026] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the Sulfate Crystalline Form A obtained using Cu-Kα radiation are shown in Table 2 below: [Table 2]
[0027] According to an embodiment of the present invention, the Sulfate Salt Crystalline Form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0028] According to an embodiment of the present invention, the Sulfate crystalline form A has one, two or three of the following characteristics: (1) The TGA curve of the sulfate salt crystalline form A shows a weight loss of about 3.53% at 150.0±3°C; (2) The DSC curve of the sulfate salt crystalline form A has an endothermic peak onset at 131.8±3°C; (3) The DSC curve of the sulfate salt crystalline form A has an endothermic peak at 141.9±10°C, and in particular, the DSC curve of the sulfate salt crystalline form A has an endothermic peak at 141.9±5°C.
[0029] According to an embodiment of the present invention, the Sulfate crystalline form A has one or two of the following characteristics: (1) The Sulfate Salt Crystalline Form A has a TGA curve essentially as shown in FIG. 21; (2) The Sulfate Salt Crystal Form A has a DSC curve essentially as shown in FIG.
[0030] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the maleate crystalline form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 4.43±0.20°, 13.86±0.20°, 14.41±0.20°, 15.00±0.20°, 22.07±0.20°, 22.65±0.20°, 25.58±0.20° and 27.34±0.20°.
[0031] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the maleate salt crystalline form A has characteristic peaks at 2θ angles of 4.43±0.20°, 9.92±0.20°, 13.86±0.20°, 14.41±0.20°, 15.00±0.20°, 17.82±0.20°, 22.07±0.20°, 22.65±0.20°, 25.58±0.20° and 27.34±0.20°.
[0032] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the maleate salt crystalline form A has characteristic peaks at 2θ angles of 4.43±0.20°, 9.92±0.20°, 13.86±0.20°, 14.41±0.20°, 15.00±0.20°, 17.82±0.20°, 22.07±0.20°, 22.65±0.20°, 24.20±0.20°, 24.53±0.20°, 25.58±0.20°, 25.84±0.20° and 27.34±0.20°.
[0033] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the maleate crystalline form A obtained using Cu-Kα radiation are shown in Table 3 below: [Table 3]
[0034] According to an embodiment of the present invention, the maleate salt crystalline form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0035] According to an embodiment of the present invention, the maleate crystalline form A has one or two of the following characteristics: (1) The TGA curve of the maleate crystalline form A shows a weight loss of about 10.48% at 150.0±3°C; (2) The DSC curve of maleate crystalline form A has two endothermic peaks at 103.0±10°C and 132.8±10°C, and in particular, the DSC curve of maleate crystalline form A has two endothermic peaks at 103.0±5°C and 132.8±5°C.
[0036] According to an embodiment of the present invention, the maleate crystalline form A has one or two of the following characteristics: (1) Maleate salt crystalline form A has a TGA curve essentially as shown in FIG. 22; (2) Maleate crystalline form A has a DSC curve essentially as shown in FIG.
[0037] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the phosphate crystalline form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.08±0.20°, 15.93±0.20°, 24.37±0.20°, and 25.19±0.20°.
[0038] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the above phosphate crystalline form A obtained using Cu-Kα radiation are shown in Table 4 below: [Table 4]
[0039] According to an embodiment of the present invention, the phosphate crystalline form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0040] According to an embodiment of the present invention, the phosphate crystalline form A has one or two of the following characteristics: (1) The TGA curve of phosphate crystalline form A shows a weight loss of about 12.68% at 150.0±3°C; (2) The DSC curve of phosphate crystalline form A has two endothermic peaks at 89.4±3°C and 94.3±3°C.
[0041] According to an embodiment of the present invention, the phosphate crystalline form A has one or two of the following characteristics: (1) Phosphate crystalline form A has a TGA curve essentially as shown in FIG. 23; (2) Phosphate crystalline form A has a DSC curve essentially as shown in FIG.
[0042] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the tartrate salt crystalline form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.00±0.20° and 15.88±0.20°.
[0043] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the tartrate salt crystalline form A has the following 2θ angles: 5.00±0.20°, 7.34±0.20°, 8.59±0.20°, 15.88±0.20°, 16.0±0.20°, 17.0±0.20°, 18.0±0.20°, 19.0±0 ±0.20° , with characteristic peaks at 19.54±0.20°, 21.46±0.20°, 23.43±0.20°, and 25.08±0.20°.
[0044] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the above Tartrate Salt Crystalline Form A obtained using Cu-Kα radiation are shown in Table 5 below: [Table 5]
[0045] According to an embodiment of the present invention, the Tartrate Salt Crystalline Form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0046] According to an embodiment of the present invention, the Tartrate Salt Crystalline Form A has one or two of the following characteristics: (1) The TGA curve of the tartrate salt crystal form A shows a weight loss of about 14.67% at 150.0±3°C; (2) The DSC curve of the tartrate salt crystalline form A has an endothermic peak at 96.8±10°C, and in particular, the DSC curve of the tartrate salt crystalline form A has an endothermic peak at 96.8±5°C.
[0047] According to an embodiment of the present invention, the Tartrate Salt Crystalline Form A has one or two of the following characteristics: (1) The tartrate salt crystalline form A has a TGA curve essentially as shown in FIG. 24; (2) The tartrate salt crystal form A has a DSC curve essentially as shown in FIG.
[0048] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the tartrate salt crystalline form B obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.24±0.20° and 23.94±0.20°.
[0049] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the above Tartrate Salt Crystalline Form B obtained using Cu-Kα radiation are shown in Table 6 below: [Table 6]
[0050] According to an embodiment of the present invention, the Tartrate Salt Crystalline Form B has an X-ray powder diffraction pattern essentially as shown in FIG.
[0051] According to an embodiment of the present invention, the Tartrate Salt Crystalline Form B has one, two or three of the following characteristics: (1) The TGA curve of the tartrate salt crystal form B shows a weight loss of about 4.87% at 150.0±3°C; (2) The DSC curve of the tartrate salt crystal form B has an endothermic peak onset at 173.9±3°C; (3) The DSC curve of the tartrate salt crystal form B has an endothermic peak at 175.3±3°C.
[0052] According to an embodiment of the present invention, the Tartrate Salt Crystalline Form B has one or two of the following characteristics: (1) Tartrate salt crystalline form B has a TGA curve essentially as shown in FIG. 25; (2) The tartrate salt crystal form B has a DSC curve essentially as shown in FIG.
[0053] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the tartrate salt crystalline form C obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 4.60±0.20°, 16.15±0.20°, and 18.13±0.20°.
[0054] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the Tartrate Salt Crystalline Form C has characteristic peaks at 2θ angles of 4.60±0.20°, 7.58±0.20°, 14.39±0.20°, 16.15±0.20°, 18.13±0.20°, 22.32±0.20°, 24.44±0.20° and 26.69±0.20°.
[0055] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the Tartrate Salt Crystalline Form C obtained using Cu-Kα radiation are shown in Table 7 below: [Table 7]
[0056] According to an embodiment of the present invention, the Tartrate Salt Crystalline Form C has an X-ray powder diffraction pattern essentially as shown in FIG.
[0057] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the fumarate crystalline form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 9.52±0.20°, 13.29±0.20°, 14.92±0.20° and 25.23±0.20°.
[0058] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the fumarate salt crystalline form A has characteristic peaks at 2θ angles of 9.52±0.20°, 13.29±0.20°, 14.92±0.20°, 19.02±0.20°, 21.39±0.20°, 25.23±0.20° and 28.07±0.20°.
[0059] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the fumarate salt crystalline form A obtained using Cu-Kα radiation are shown in Table 8 below: [Table 8]
[0060] According to an embodiment of the present invention, the fumarate salt crystalline form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0061] According to an embodiment of the present invention, the Fumarate Crystalline Form A has one, two, three or four of the following characteristics: (1) The TGA curve of the fumarate salt crystalline form A shows a weight loss of about 3.86% at 150.0±3°C; (2) The DSC curve of the fumarate salt crystalline form A has an endothermic peak onset at 208.6±3°C; (3) The DSC curve of the fumarate salt crystalline form A has an endothermic peak at 210.2±3°C; (4) The DVS curve of the fumarate crystalline form A has a water adsorption of less than about 1%, for example less than about 0.8%, particularly less than about 0.60%, under conditions of 0% RH to 80% RH.
[0062] According to an embodiment of the present invention, the Fumarate Crystalline Form A has one, two or three of the following characteristics: (1) Fumarate crystalline form A has a TGA curve essentially as shown in FIG. 26; (2) Fumarate crystalline form A has a DSC curve essentially as shown in FIG. 26; (3) The fumarate salt crystalline form A has a DVS curve essentially as shown in FIG.
[0063] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the Citrate Crystal Form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 4.96±0.20° and 15.76±0.20°.
[0064] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the Citrate Salt Crystalline Form A obtained using Cu-Kα radiation are shown in Table 9 below: [Table 9]
[0065] According to an embodiment of the present invention, the Citrate Salt crystalline form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0066] According to an embodiment of the present invention, the Citrate Salt crystalline form A has one or two of the following characteristics: (1) The TGA curve of the citrate salt crystalline form A shows a weight loss of about 10.24% at 150.0±3°C; (2) The DSC curve of the citrate salt crystalline form A has an endothermic peak at 91.2±5°C, and in particular, the DSC curve of the citrate salt crystalline form A has an endothermic peak at 91.2±3°C.
[0067] According to an embodiment of the present invention, the Citrate Salt crystalline form A has one or two of the following characteristics: (1) Citrate Salt crystalline form A has a TGA curve essentially as shown in FIG. 27; (2) Citrate Salt Crystal Form A has a DSC curve essentially as shown in FIG.
[0068] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the glycolate crystalline form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.26±0.20°, 7.27±0.20°, 14.12±0.20°, 16.02±0.20° and 24.11±0.20°.
[0069] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the glycolate crystalline form A obtained using Cu-Kα radiation are shown in Table 10 below: [Table 10]
[0070] According to an embodiment of the present invention, the glycolate salt crystalline form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0071] According to an embodiment of the present invention, the glycolate crystalline form A has one or two of the following characteristics: (1) The TGA curve of the glycolate crystalline form A shows a weight loss of about 7.72% at 150.0±3°C; (2) The DSC curve of crystalline form A of the glycolate salt has an endothermic peak at 103.1±15°C, and in particular, the DSC curve of crystalline form A of the glycolate salt has an endothermic peak at 103.1±10°C.
[0072] According to an embodiment of the present invention, the glycolate crystalline form A has one or two of the following characteristics: (1) The glycolate salt crystalline form A has a TGA curve essentially as shown in FIG. 28; (2) The glycolate salt crystalline form A has a DSC curve essentially as shown in FIG.
[0073] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the succinate crystalline form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.26±0.20°, 14.00±0.20°, 15.76±0.20°, 21.07±0.20°, 22.00±0.20° and 27.08±0.20°.
[0074] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the succinate crystalline form A has characteristic peaks at 2θ angles of 5.26±0.20°, 6.99±0.20°, 7.35±0.20°, 14.00±0.20°, 15.76±0.20°, 21.07±0.20°, 22.00±0.20° and 27.08±0.20°.
[0075] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the succinate crystalline form A obtained using Cu-Kα radiation are shown in Table 11 below: [Table 11]
[0076] According to an embodiment of the present invention, the succinate salt crystalline form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0077] According to an embodiment of the present invention, the succinate crystalline form A has one or two of the following characteristics: (1) The TGA curve of succinate crystalline form A shows a weight loss of about 3.74% at 150.0±3°C; (2) The DSC curve of succinate crystalline form A has four endothermic peaks at 73.3±10°C, 102.2±10°C, 136.6±10°C and 173.6±10°C, and in particular, the DSC curve of succinate crystalline form A has four endothermic peaks at 73.3±5°C, 102.2±5°C, 136.6±5°C and 173.6±5°C.
[0078] According to an embodiment of the present invention, the succinate crystalline form A has one or two of the following characteristics: (1) The succinate salt crystalline form A has a TGA curve essentially as shown in FIG. 29; (2) The succinate salt crystalline form A has a DSC curve essentially as shown in FIG.
[0079] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the succinate crystalline form B obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 9.54±0.20°, 12.60±0.20°, 14.91±0.20°, 19.17±0.20°, 21.02±0.20° and 24.88±0.20°.
[0080] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the succinate crystalline form B has characteristic peaks at 2θ angles of 9.54±0.20°, 12.60±0.20°, 13.28±0.20°, 14.91±0.20°, 15.20±0.20°, 19.17±0.20°, 21.02±0.20°, 24.88±0.20° and 28.15±0.20°.
[0081] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the succinate crystalline form B has characteristic peaks at 2θ angles of 9.54±0.20°, 12.60±0.20°, 13.28±0.20°, 14.91±0.20°, 15.20±0.20°, 19.17±0.20°, 19.77±0.20°, 21.02±0.20°, 21.44±0.20°, 24.88±0.20°, 25.22±0.20° and 28.15±0.20°.
[0082] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the succinate crystalline form B obtained using Cu-Kα radiation are shown in Table 12 below: [Table 12]
[0083] According to an embodiment of the present invention, the succinate salt crystalline form B has an X-ray powder diffraction pattern essentially as shown in FIG.
[0084] According to an embodiment of the present invention, the succinate crystalline form B has one, two or three of the following characteristics: (1) The TGA curve of succinate crystalline form B shows a weight loss of about 0.83% at 150.0±3°C; (2) The DSC curve of the succinate crystalline form B has an endothermic peak onset at 128.8±3°C; (3) The DSC curve of the succinate crystalline form B has an endothermic peak at 129.9±3°C.
[0085] According to an embodiment of the present invention, the succinate crystalline form B has one or two of the following characteristics: (1) The succinate salt crystalline form B has a TGA curve essentially as shown in FIG. 30; (2) The succinate salt crystalline form B has a DSC curve essentially as shown in FIG.
[0086] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the adipate crystalline form B obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 4.98±0.20°, 10.69±0.20°, 13.88±0.20°, 21.41±0.20°, 24.97±0.20° and 26.15±0.20°.
[0087] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the adipate crystalline form B has characteristic peaks at 2θ angles of 4.98±0.20°, 10.69±0.20°, 13.88±0.20°, 14.28±0.20°, 20.72±0.20°, 21.41±0.20°, 24.97±0.20° and 26.15±0.20°.
[0088] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the adipate crystalline form B has characteristic peaks at 2θ angles of 4.98±0.20°, 9.23±0.20°, 10.69±0.20°, 13.88±0.20°, 14.28±0.20°, 19.35±0.20°, 20.72±0.20°, 21.41±0.20°, 24.97±0.20° and 26.15±0.20°.
[0089] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the adipate crystalline form B obtained using Cu-Kα radiation are shown in Table 13 below: [Table 13]
[0090] According to an embodiment of the present invention, the adipate crystalline form B has an X-ray powder diffraction pattern essentially as shown in FIG.
[0091] According to an embodiment of the present invention, the adipate crystalline form B has one, two or three of the following characteristics: (1) The TGA curve of the adipate salt crystalline form B shows a weight loss of about 1.23% at 150.0±3°C; (2) The DSC curve of the adipate salt crystal form B has an endothermic peak onset at 112.8±3°C; (3) The DSC curve of the adipate salt crystalline form B has an endothermic peak at 115.6±3°C.
[0092] According to an embodiment of the present invention, the adipate crystalline form B has one or two of the following characteristics: (1) The adipate salt crystalline form B has a TGA curve essentially as shown in FIG. 31; (2) The adipate salt crystalline form B has a DSC curve essentially as shown in FIG.
[0093] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the crystalline form A of said sebacate salt obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 4.57±0.20°, 9.27±0.20°, 11.20±0.20°, 14.40±0.20°, 20.16±0.20°, 24.63±0.20° and 26.73±0.20°.
[0094] According to an embodiment of the present invention, the X-ray powder diffraction pattern of said crystalline form A of sebacate has characteristic peaks at 2θ angles of 4.57±0.20°, 9.27±0.20°, 11.20±0.20°, 14.40±0.20°, 14.95±0.20°, 20.16±0.20°, 20.55±0.20°, 22.95±0.20°, 23.91±0.20°, 24.63±0.20° and 26.73±0.20°.
[0095] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the crystalline form A of the sebacate salt has characteristic peaks at 2θ angles of 4.57±0.20°, 9.27±0.20°, 11.20±0.20°, 14.40±0.20°, 14.95±0.20°, 15.26±0.20°, 18.25±0.20°, 20.16±0.20°, 20.95±0.20°, 22.95±0.20°, 23.91±0.20°, 24.63±0.20° and 26.73±0.20°.
[0096] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the above sebacic acid salt crystalline form A obtained using Cu-Kα radiation are shown in Table 14 below: [Table 14]
[0097] According to an embodiment of the present invention, the sebacate crystalline form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0098] According to an embodiment of the present invention, the crystalline form A of the sebacate salt has one or two of the following characteristics: (1) The TGA curve of the crystalline form A of the sebacate salt shows a weight loss of about 0.45% at 150.0±3°C; (2) The DSC curve of the crystalline form A of the sebacate salt has two endothermic peaks at 80.9±10°C and 142.1±10°C.
[0099] According to an embodiment of the present invention, the crystalline form A of the sebacate salt has one or two of the following characteristics: (1) The crystalline form A of the sebacate salt has a TGA curve essentially as shown in FIG. 32; (2) The sebacate crystalline form A has a DSC curve essentially as shown in FIG.
[0100] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the p-toluenesulfonate crystalline form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 6.04±0.20°, 8.59±0.20°, 14.27±0.20°, 17.14±0.20° and 25.29±0.20°.
[0101] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the p-toluenesulfonate crystalline form A has characteristic peaks at 2θ angles of 6.04±0.20°, 8.59±0.20°, 14.27±0.20°, 17.14±0.20°, 20.41±0.20°, 23.68±0.20°, 25.29±0.20° and 27.65±0.20°.
[0102] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the p-toluenesulfonate crystalline form A has characteristic peaks at 2θ angles of 6.04±0.20°, 8.59±0.20°, 12.28±0.20°, 14.27±0.20°, 16.02±0.20°, 17.14±0.20°, 20.41±0.20°, 22.01±0.20°, 23.68±0.20°, 25.29±0.20° and 27.65±0.20°.
[0103] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the p-toluenesulfonate crystalline form A obtained using Cu-Kα radiation are shown in Table 15 below: [Table 15]
[0104] According to an embodiment of the present invention, the p-toluenesulfonate crystalline form A has an X-ray diffraction pattern essentially as shown in FIG.
[0105] According to an embodiment of the present invention, the p-toluenesulfonate crystalline form A has one or two of the following characteristics: (1) The TGA curve of p-toluenesulfonate crystalline form A shows a weight loss of about 3.29% at 150.0±3°C; (2) The DSC curve of p-toluenesulfonate crystalline form A has an endothermic peak at 210.8±10°C, and in particular, the DSC curve of p-toluenesulfonate crystalline form A has an endothermic peak at 210.8±5°C.
[0106] More specifically, the DSC curve of the p-toluenesulfonate crystalline form A further has an endothermic peak at 72.7±10°C, particularly at 72.7±5°C.
[0107] According to an embodiment of the present invention, the p-toluenesulfonate crystalline form A has one or two of the following characteristics: (1) p-Toluenesulfonate crystalline form A has a TGA curve essentially as shown in FIG. 33; (2) p-Toluenesulfonate crystalline form A has a DSC curve essentially as shown in FIG.
[0108] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the benzenesulfonate salt crystalline form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 6.16±0.20°, 8.98±0.20°, 14.22±0.20°, 16.90±0.20°, 18.31±0.20°, 20.92±0.20°, 25.11±0.20° and 26.29±0.20°.
[0109] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the benzenesulfonate salt crystalline form A has characteristic peaks at 2θ angles of 6.16±0.20°, 8.98±0.20°, 14.22±0.20°, 15.67±0.20°, 16.90±0.20°, 17.55±0.20°, 18.31±0.20°, 20.34±0.20°, 20.92±0.20°, 25.11±0.20°, 26.29±0.20° and 29.24±0.20°.
[0110] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the benzenesulfonate salt crystalline form A has characteristic peaks at 2θ angles of 6.16±0.20°, 8.98±0.20°, 14.22±0.20°, 15.67±0.20°, 16.90±0.20°, 17.55±0.20°, 18.31±0.20°, 20.34±0.20°, 20.92±0.20°, 23.54±0.20°, 24.65±0.20°, 25.11±0.20°, 26.29±0.20° and 29.24±0.20°.
[0111] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the benzenesulfonate salt crystalline form A obtained using Cu-Kα radiation are shown in Table 16 below: [Table 16]
[0112] According to an embodiment of the present invention, the benzenesulfonate salt crystalline form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0113] According to an embodiment of the present invention, the benzenesulfonate salt crystalline form A has one, two, three or four of the following characteristics: (1) The TGA curve of the benzenesulfonate salt crystalline form A shows a weight loss of about 1.87% at 150.0±3°C; (2) The DSC curve of the benzenesulfonate salt crystalline form A has an endothermic peak onset at 184.7±3°C; (3) The DSC curve of the benzenesulfonate salt crystalline form A has an endothermic peak at 187.0±3°C; (4) The DVS curve of the benzenesulfonate crystalline form A has a water adsorption of less than about 2%, for example less than about 1.8%, particularly less than about 1.46%, under conditions of 0% RH to 80% RH.
[0114] According to an embodiment of the present invention, the benzenesulfonate salt crystalline form A has one, two or three of the following characteristics: (1) The benzenesulfonate salt crystalline form A has a TGA curve essentially as shown in FIG. 34; (2) The benzenesulfonate salt crystalline form A has a DSC curve essentially as shown in FIG. 34; (3) The benzenesulfonate salt crystalline form A has a DVS curve essentially as shown in FIG.
[0115] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the hydrobromide salt crystalline form A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 9.54±0.20° and 24.63±0.20°.
[0116] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the hydrobromide salt crystalline form A obtained using Cu-Kα radiation are shown in Table 17 below: [Table 17]
[0117] According to an embodiment of the present invention, the hydrobromide salt crystalline form A has an X-ray powder diffraction pattern essentially as shown in FIG.
[0118] According to an embodiment of the present invention, the hydrobromide salt crystalline form A has one or two of the following characteristics: (1) The TGA curve of the hydrobromide salt crystalline form A shows a weight loss of about 7.86% at 150.0±3°C; (2) The DSC curve of the hydrobromide salt crystalline form A has three endothermic peaks at 96.5±5°C, 107.3±5°C and 141.8±5°C.
[0119] According to an embodiment of the present invention, the hydrobromide salt crystalline form A has one or two of the following characteristics: (1) Hydrobromide salt crystalline form A has a TGA curve essentially as shown in FIG. 35; (2) The hydrobromide salt crystalline form A has a DSC curve essentially as shown in FIG.
[0120] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the hydrobromide salt crystalline form B obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 9.48±0.20°, 15.89±0.20°, and 23.98±0.20°.
[0121] According to an embodiment of the present invention, the X-ray powder diffraction pattern of the hydrobromide salt crystalline form B has characteristic peaks at 2θ angles of 9.48±0.20°, 15.89±0.20°, 19.40±0.20°, 23.98±0.20°, 26.55±0.20° and 28.02±0.20°.
[0122] According to an embodiment of the present invention, the 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the hydrobromide salt crystalline form B obtained using Cu-Kα radiation are shown in Table 18 below: [Table 18]
[0123] According to an embodiment of the present invention, the hydrobromide salt crystalline form B has an X-ray powder diffraction pattern essentially as shown in FIG.
[0124] According to an embodiment of the present invention, the hydrobromide salt crystalline form B has one or two of the following characteristics: (1) The TGA curve of the hydrobromide salt crystalline form B shows a weight loss of about 4.95% at 150.0±3°C; (2) The DSC curve of hydrobromide crystalline form B has three endothermic peaks at 81.6±10°C, 128.9±10°C and 163.6±10°C, and in particular, the DSC curve of hydrobromide crystalline form B has three endothermic peaks at 81.6±5°C, 128.9±5°C and 163.6±5°C.
[0125] According to an embodiment of the present invention, the hydrobromide salt crystalline form B has one or two of the following characteristics: (1) Hydrobromide salt crystalline form B has a TGA curve essentially as shown in FIG. 36; (2) The hydrobromide salt crystalline form B has a DSC curve essentially as shown in FIG.
[0126] The present invention further provides a process for preparing a salt of a compound of formula (I) comprising the step of contacting a compound of formula (I) with an inorganic or organic acid: [ka]
[0127] According to an embodiment of the present invention, the inorganic or organic acid is independently selected from the above definitions.
[0128] According to an embodiment of the present invention, the molar ratio of the compound of formula (I) to the inorganic acid or organic acid may be 1:(0.5-5), for example 1:(0.5-2), illustratively 1:0.5 or 1:1.
[0129] The present invention further provides a method for preparing a crystalline form of a salt of the compound of formula (I), comprising the steps of stirring the compound of formula (I) and a corresponding inorganic or organic acid in a solvent at room temperature, transferring the clear sample to 5°C to -20°C and stirring, transferring the clear sample to room temperature and evaporating the solvent.
[0130] According to an embodiment of the present invention, the inorganic or organic acid is independently selected from the above definitions.
[0131] According to an embodiment of the present invention, the molar ratio of the compound of formula (I) to the inorganic acid or organic acid may be 1:(0.5-5), for example 1:(0.5-2), illustratively 1:0.5 or 1:1.
[0132] The present invention further provides pharmaceutical compositions comprising a salt of a compound of formula (I) in a solid form, such as a crystalline or amorphous form thereof.
[0133] According to an embodiment of the present invention, the pharmaceutical composition may further comprise a pharma- ceutically acceptable auxiliary material, such as a carrier or excipient.
[0134] According to an embodiment of the invention, in said pharmaceutical composition, the salt of the compound of formula (I) is present in a therapeutically effective amount.
[0135] The present invention further provides the use of the salt of the compound of formula (I) in solid form, such as its crystalline or amorphous form, in the manufacture of a medicament.Preferably, the medicament is used for the treatment and / or prevention of ATX-related diseases.
[0136] The present invention further provides a method for preventing and / or treating an autotaxin ATX-associated disease, comprising administering to a patient in need thereof a therapeutically effective amount of a salt of the compound of formula (I) in a solid form, such as a crystalline or amorphous form, or the pharmaceutical composition.
[0137] The present invention further provides a salt of a compound of formula (I) in a solid form, such as a crystalline or amorphous form thereof, or a pharmaceutical composition as described above, for treating and / or preventing an autotaxin (ATX)-associated disease.
[0138] According to an embodiment of the present invention, the ATX-related disease includes at least one selected from cancer, metabolic disease, kidney disease, liver disease, fibrodegenerative disease, interstitial lung disease, proliferative disease, inflammatory disease, pain, autoimmune disease, respiratory disease, cardiovascular disease, neurodegenerative disease, dermatological disorder, and / or disease associated with abnormal angiogenesis.
[0139] According to an embodiment of the present invention, the ATX-associated disease includes at least one selected from interstitial lung disease, pulmonary fibrosis, liver fibrosis, and renal fibrosis.
[0140] According to an embodiment of the present invention, the ATX-associated disease includes idiopathic pulmonary fibrosis.
[0141] According to an embodiment of the present invention, the ATX-associated disease includes type 2 diabetes and non-alcoholic steatohepatitis.
[0142] According to an embodiment of the present invention, the ATX-associated disease includes neuropathic pain and inflammatory pain.
[0143] According to an embodiment of the present invention, the ATX-associated disease includes pain associated with osteoarthritis.
[0144] As a drug, the salt of the present invention or its solid form may be administered in the form of a pharmaceutical composition. These compositions can be prepared according to methods well known in the pharmaceutical art and can be administered via various routes depending on whether local or systemic treatment is required and the area to be treated. They can be administered topically (e.g., transdermally, including intranasally, vaginally and rectally, to the skin, eyes and mucous membranes), pulmonary (e.g., intratracheally, intranasally by inhaling or blowing a powder or aerosol, including by nebulizer), orally or parenterally. Parenteral administration includes intravenous, intraarterial, subcutaneous, intraperitoneal or intramuscular injection or infusion, or intracranial administration, e.g., intrathecal or intraventricular. Parenteral administration can be in the form of a single bolus or, for example, by a continuous perfusion pump. Pharmaceutical compositions and formulations administered topically can include transdermal patches, ointments, lotions, creams, gels, drops, suppositories, sprays, liquids and powders. Conventional drug carriers, water, powder or oily bases, thickeners and the like may be necessary or required.
[0145] When preparing the compositions of the present invention, the active ingredient (i.e., the salt of the present invention or a solid form thereof) is usually mixed with an excipient and diluted or loaded into a carrier such as a capsule, sachet, paper or other container form by the excipient. When an excipient is used as a diluent, it may be a solid, semi-solid or liquid substance used as a solvent, carrier or medium for the active ingredient. Thus, the compositions may be in the form of tablets, pills, powders, topical applications, sachets, cachets, elixirs, suspensions, emulsions, solutions, syrups, aerosols (solvents dissolved in solids or liquids), ointments containing, for example, up to 10% by weight of the active ingredient, soft and hard gelatin capsules, suppositories, sterile injection solutions and sterile packaged powders.
[0146] Some examples of suitable excipients include lactose, glucose, sucrose, sorbitol, mannitol, starch, gum arabic, calcium phosphate, alginate, tragacanth, gelatin, calcium silicate, microcrystalline cellulose, polyvinylpyrrolidone, cellulose, water, syrup, and methylcellulose. The formulation may further include lubricants such as talc, magnesium stearate, and mineral oil, wetting agents, emulsifying and suspending agents, preservatives such as methyl benzoate and hydroxypropyl benzoate, sweeteners, and flavoring agents. The compositions of the present invention can be prepared using methods known in the art to provide immediate, sustained, or delayed release of the active ingredient after administration to a patient.
[0147] The compositions can be prepared in unit dosage form, each dose containing about 5 to 1200 mg, more usually about 50 to 800 mg, of active ingredient. The term "unit dosage form" refers to physically discrete single dosage units suitable for human patients and other mammals, each unit containing a predetermined quantity of active material calculated to produce a desired therapeutic effect, mixed with a suitable pharmaceutical excipient.
[0148] The effective dosage range of the active compound may be very large and is usually administered in a pharmacologic effective amount. However, it is understood that the amount of the compound actually administered will usually be determined by the physician depending on the relevant circumstances, including the condition being treated, the route of administration selected, the actual compound being administered, the age, weight and response of the individual patient, and the severity of the patient's symptoms.
[0149] When preparing solid compositions such as tablets, the primary active ingredient and pharmaceutical excipients are mixed to form a solid preformulation composition containing a homogenous mixture of the salt of the invention or a solid form thereof. When these preformulation compositions are referred to as homogenous, it is meant that the active ingredient is generally uniformly distributed throughout the composition such that the composition may be readily divided into equally effective unit dosage forms such as tablets, pills, and capsules. The solid preformulation is then divided into unit dosage forms of the types described above, for example containing about 0.1 to 1000 mg of the active ingredient of the invention.
[0150] The tablet or pill of the present invention can be coated or compounded to obtain a dosage form that provides the advantage of sustained action.For example, the tablet or pill can include an inner dosage component and an outer dosage component, the latter being a coating of the former.The two components can be separated by an enteric layer, which is intended to prevent disintegration in the stomach so that the inner component passes completely through the duodenum or is delayed in release.Such enteric layers or coatings can use a variety of materials, including a variety of polymeric acids and mixtures of polymeric acids with materials such as shellac, cetyl alcohol, and cellulose acetate.
[0151] Orally or injectable liquid forms into which the salts of the invention or solid forms and compositions thereof may be incorporated include aqueous solutions, suitably flavored syrups, aqueous or oily suspensions, emulsions flavored with edible oils such as cottonseed oil, sesame oil, coconut oil or peanut oil, elixirs and similar pharmaceutical vehicles.
[0152] Compositions for inhalation or blowing include solutions and suspensions in pharma- ceutically acceptable water or organic solvents or mixtures thereof, and powders. Liquid or solid compositions may contain suitable pharma- ceutically acceptable excipients as described above. In some embodiments, the compositions are administered by oral or nasal respiratory route to achieve a local or systemic effect. The compositions may be nebulized using an inert gas. The nebulized solution may be directly inhaled by the nebulizing device, or the nebulizing device may be connected to a face mask tent or intermittent positive pressure respirator. The solution, suspension, or powder compositions may be administered orally or nasally from a device that delivers the formulation in an appropriate manner.
[0153] The amount of the salt or solid form or composition thereof administered to a patient will vary and will depend on the drug being administered, the purpose for which it is being administered, such as prophylaxis or treatment, the condition of the patient, the mode of administration, etc. In therapeutic applications, a sufficient amount of the composition may be administered to a patient suffering from a disease to cure or at least partially arrest the symptoms of the disease and its complications. The effective dose will depend on the condition of the disease being treated and the judgment of the attending clinician, which will depend on factors such as the severity of the disease, the age, weight, and general condition of the patient.
[0154] The compositions administered to a patient may be in the form of pharmaceutical compositions described above. These compositions may be sterilized by conventional sterilization techniques or sterile filtration. The aqueous solutions may be packaged as is or lyophilized and the lyophilized formulation may be mixed with a sterile aqueous carrier prior to administration. The pH of the compound formulation is usually 3-11, more preferably 5-9, and most preferably 7-8. It is understood that the use of some of the excipients, carriers, or stabilizers described above may result in the formation of pharmaceutical salts.
[0155] The therapeutic dosage of a salt of the invention or a solid form thereof can be determined, for example, by the specific therapeutic application, the manner in which the compound is administered, the health and condition of the patient, and the judgment of the prescribing physician. The proportion or concentration of a compound of the invention in a pharmaceutical composition is variable and depends on a variety of factors, including dosage amount, chemical properties (e.g., hydrophobicity), and route of administration. For example, a compound of the invention can be provided for parenteral administration by an aqueous physiological buffer solution containing about 0.1-10% w / v of the compound. Some typical dosage ranges are about 1 μg / kg to about 1 g / kg body weight / day. In some embodiments, the dosage range is about 0.01 mg / kg to about 100 mg / kg body weight / day. The dosage is likely to depend on variables such as the type and progression of the disease or condition, the general health of the particular patient, the relative biological potency of the compound selected, the excipient formulation, and its route of administration. Effective dosages can be obtained by extrapolation from dose-response curves derived from in vitro or animal model test systems.
[0156] [Definition and Interpretation of Terms] Unless otherwise specified, the definitions of groups and terms described in the specification and claims of this application include exemplary definitions, exemplary definitions, preferred definitions, definitions described in the tables, definitions of specific compounds in the examples, etc., and can be combined or combined with each other in any way. The definitions and compound structures after such combination or combination should be included in the scope described in the specification of this application.
[0157] Unless otherwise specified, the numerical ranges described in the present specification and claims are equivalent to at least listing each specific integer value therein. For example, 2 or more means 2, 3, 4, 5, 6, 7, 8, 9, 10 or more. When some numerical ranges are defined or understood as "numbers", it should be understood that the two end points of the range, each integer within the range, and each decimal within the range are listed. For example, "numbers from 0 to 10" should be understood to not only list each integer of 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, and 10, but also to list at least each integer plus 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9.
[0158] In the present specification and claims, when "about" is used in relation to a certain numerical value, it includes the numerical value itself and numerical values within a range around the numerical value that is acceptable in the art, such as numerical values within ±15% of the numerical value, numerical values within ±10% of the numerical value, numerical values within ±5% of the numerical value, etc. For example, about 10 represents numerical values within the range of 10±1.5, i.e., within the range of 8.5 to 11.5, within the range of 10±1.0, i.e., within the range of 9.0 to 11.0, and within the range of 10±0.5, i.e., within the range of 9.5 to 10.5.
[0159] The term "patient" refers to any animal, including a mammal, preferably a mouse, rat, other rodent, rabbit, dog, cat, pig, cow, sheep, horse or primate, and most preferably a human.
[0160] The term "therapeutically effective amount" refers to an amount of an active compound or drug that elicits the biological or medical response that a researcher, veterinarian, physician, or other clinician is looking for in a tissue, system, animal, individual, or human, including one or more of the following: (1) prevention of disease: e.g., prevention of a disease, disorder, or condition in an individual who is susceptible to the disease, disorder, or condition, but has not yet experienced or developed the pathology or symptoms of the disease; (2) inhibition of disease: e.g., inhibition of a disease, disorder, or condition (i.e., prevention of further progression of the pathology and / or symptoms) in an individual who is experiencing or developing the pathology or symptoms of the disease, disorder, or condition; (3) mitigation of disease: e.g., mitigation of a disease, disorder, or condition (i.e., reversal of the pathology and / or symptoms) in an individual who is experiencing or developing the pathology or symptoms of the disease, disorder, or condition.
[0161] The term "pharmaceutical acceptable" means that the formulation or active ingredient does not have undue adverse effects on the health of the general therapeutic target.
[0162] The term "pharmacologically acceptable excipient or carrier" refers to one or more compatible solid or liquid fillers or gel substances that must be suitable for human use and have sufficient purity and sufficiently low toxicity. "Compatibility" here means that the components of the composition can be mixed with the compounds of the present invention and with each other without appreciably reducing the efficacy of the compounds. Examples of pharmacologically acceptable excipient or carrier moieties include cellulose and its derivatives (sodium carboxymethylcellulose, sodium ethylcellulose, cellulose acetate, etc.), gelatin, talc, solid lubricants (stearic acid, magnesium stearate, etc.), calcium sulfate, vegetable oils (soybean oil, sesame oil, peanut oil, olive oil, etc.), polyols (propylene glycol, glycerol, mannitol, sorbitol, etc.), emulsifiers, wetting agents (sodium lauryl sulfate, etc.), colorants, flavor enhancers, stabilizers, antioxidants, preservatives, pyrogen-free water, etc. Effect of the Invention
[0163] The salt of compound of formula (I) according to the present invention and its crystalline form have good solubility, stability and hygroscopicity.For example, the crystalline form A of the benzenesulfonate salt of compound of formula (I) has the following advantages:(1) it is weakly hygroscopic, does not undergo crystal transformation after DVS test, and is easy to control the CMC of drug formation, providing a material basis for formulation development;(2) it has uniform particle size, and the particle size under PLM is less than 50 μm, and the crystallization process can effectively remove impurities in the reaction process, improve production efficiency and reduce production costs;(3) it has obviously improved solubility, which is suitable for drug development and has clinical benefits;(4) it has better solid stability.
[0164] Therefore, the salts and their crystalline forms provided by the present invention are more suitable for pharmaceutical use, and their preparation methods are simple, feasible, and suitable for mass production. [Brief description of the drawings]
[0165] [Figure 1] FIG. 2 is an XRPD pattern (Instrument 2) of the hydrochloride salt crystalline form A of compound of formula (I). [Diagram 2] FIG. 2 is an XRPD pattern (Instrument 2) of sulfate salt crystalline form A of compound of formula (I). [Diagram 3] FIG. 1 is an XRPD pattern (Instrument 3) of the maleate salt crystalline form A of compound of formula (I). [Figure 4] FIG. 2 is an XRPD pattern (Instrument 2) of phosphate salt crystalline form A of compound of formula (I). [Diagram 5] FIG. 2 is an XRPD pattern (Instrument 2) of crystalline Form A of the tartrate salt of compound of formula (I). [Figure 6] FIG. 2 is an XRPD pattern (Instrument 2) of crystalline form B of the tartrate salt of compound of formula (I). [Figure 7] FIG. 1 is an XRPD pattern (Instrument 3) of crystalline Form C of the tartrate salt of compound of formula (I). [Figure 8] FIG. 2 is an XRPD pattern (Instrument 2) of the fumarate salt crystalline form A of compound of formula (I). [Figure 9] FIG. 2 is an XRPD pattern (Instrument 2) of crystalline form A of the citrate salt of compound of formula (I). [Figure 10] FIG. 2 is an XRPD pattern (Instrument 2) of crystalline form A of the glycolate salt of compound of formula (I). [Figure 11] FIG. 1 is an XRPD pattern (Instrument 3) of succinate crystalline form A of compound of formula (I). [Figure 12] FIG. 1 is an XRPD pattern (Instrument 1) of succinate crystalline form B of compound of formula (I). [Figure 13] FIG. 2 is an XRPD pattern (Instrument 2) of the adipate salt crystalline form B of compound of formula (I). [Figure 14] FIG. 1 is an XRPD pattern (Instrument 1) of crystalline form A of the sebacate salt of compound of formula (I). [Figure 15] FIG. 2 is an XRPD pattern (Instrument 2) of p-toluenesulfonate crystalline form A of compound of formula (I). [Figure 16] FIG. 1 is an XRPD pattern (Instrument 1) of crystalline form A of the benzenesulfonate salt of compound of formula (I). [Figure 17] FIG. 2 is an XRPD pattern (Instrument 2) of crystalline Form A of the hydrobromide salt of compound of formula (I). [Figure 18] FIG. 1 is an XRPD pattern (Instrument 1) of the hydrobromide salt crystalline form B of compound of formula (I). [Figure 19] 1 is an XRPD overlay pattern (instrument 2) of a stability evaluation sample of benzenesulfonate crystalline form A of compound of formula (I). [Figure 20] 1 is a TGA / DSC pattern of the hydrochloride crystal form A of compound (I). [Figure 21] 1 is a TGA / DSC pattern of the sulfate crystalline form A of compound (I). [Figure 22] 1 is a TGA / DSC pattern of the maleate crystalline form A of compound (I). [Figure 23] 1 is a TGA / DSC pattern of phosphate crystal form A of compound (I). [Figure 24] 1 is a TGA / DSC pattern of the tartrate salt of compound (I), crystalline form A. [Diagram 25] 1 is a TGA / DSC pattern of the tartrate salt crystal form B of compound (I). [Figure 26] 1 is a TGA / DSC pattern of the fumarate salt of compound (I) in crystalline form A. [Figure 27] 1 is a TGA / DSC pattern of the citrate crystal form A of compound (I). [Figure 28] 1 is a TGA / DSC pattern of the glycolate crystal form A of compound (I). [Figure 29] 1 is a TGA / DSC pattern of succinate crystal form A of compound (I). [Diagram 30] 1 is a TGA / DSC pattern of succinate crystal form B of compound (I). [Diagram 31] 1 is a TGA / DSC pattern of the adipate crystal form B of compound (I). [Diagram 32] 1 is a TGA / DSC pattern of the sebacate crystal form A of compound (I). [Diagram 33] FIG. 2 is a TGA / DSC pattern of p-toluenesulfonate crystal form A of compound (I). [Diagram 34] 1 is a TGA / DSC pattern of the benzenesulfonate crystal form A of compound (I). [Diagram 35] 1 is a TGA / DSC pattern of the hydrobromide salt of compound (I) in crystalline form A. [Diagram 36] 1 is a TGA / DSC pattern of the hydrobromide salt of compound (I) in crystalline form B. [Figure 37] 1 is a DVS pattern of the hydrochloride crystal form A of compound (I). [Figure 38] 1 is a DVS pattern of the fumarate crystal form A of compound (I). [Figure 39] 1 is a DVS pattern of the benzenesulfonate crystal form A of compound (I). [Diagram 40] FIG. 1 is an XRPD pattern (Instrument 1) of the free base crystalline form A of compound (I). [Diagram 41] FIG. 2 is a TGA / DSC pattern of the free base crystalline form A of compound (I). [Diagram 42]FIG. 1 is a DVS pattern of the free base crystalline form A of compound (I). [Diagram 43] 1 shows the body weight change curve of animals after administration in Test Example 7 of the present invention. [Diagram 44] FIG. 1 is a graph showing changes in TGF-β1 content in lung tissue and bronchoalveolar lavage fluid after administration in Test Example 7 of the present invention. EXAMPLES
[0166] The salt form of the compound of formula (I) according to the present invention and its crystalline form, preparation method and application thereof will be described in more detail below with reference to specific examples. The following examples are merely for illustrative purposes and interpretation of the present invention, and should not be interpreted as limiting the scope of the claims of the present invention. Any technology realized based on the above content of the present invention is included in the scope of the claims of the present invention.
[0167] Unless otherwise specified, all materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0168] Crystalline Form Detection Apparatus and Method 1. X-ray Powder Diffraction (XRPD) XRPD patterns were collected on a PANalytacal X-ray powder diffraction analyzer and the scan parameters are shown in Table 19-1 below. [Table 19-1]
[0169] 2. Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC) TGA and DSC patterns were collected on a TA Q5000 / 5500 Thermogravimetric Analyzer and a TA 2500 Differential Scanning Calorimeter, respectively, with the test parameters listed in Table 19-2 below. [Table 19-2]
[0170] 3. Liquid nuclear magnetic resonance (Solution NMR): Liquid state nuclear magnetic resonance spectra were collected on a Bruker 400M nuclear magnetic resonance instrument using DMSO-d6 as the solvent.
[0171] 4. High Performance Liquid Chromatography (HPLC): The purity test, solubility and stability test in the study were performed by Agilent 1260 high performance liquid chromatograph. The analytical conditions are shown in Table 19-3 below. [Table 19-3]
[0172] 5. Dynamic Water Sorption (DVS): Dynamic moisture sorption (DVS) curves were collected on a Surface Measurement Systems (SMS) DVS Intrinsic. Relative humidity at 25°C was corrected for the deliquescence points of LiCl, Mg(NO3)2, and KCl. DVS test parameters are shown in Table 19-4 below. [Table 19-4]
[0173] 6. Polarized Light Microscopy (PLM) Polarized light microscopy data were collected at room temperature using an Axio Lab. A1 upright microscope.
[0174] 7. High performance liquid chromatography / ion chromatography (HPLC / IC). The purity test, dynamic solubility and stability test in the study were performed by Agilent 1260 high performance liquid chromatograph, and the test of salt formation molar ratio of ions was performed by ion chromatography. The analysis conditions are shown in Table 19-5 and Table 19-6 below: [Table 19-5] [Table 19-6]
[0175] Example 1: Preparation of Compounds of Formula (I) (R)-2-((1-(1H-1,2,3-triazol-5-yl)propan-2-yl)oxy)-1-(2-((2,3-dihydro-1H-inden-2-yl)amino)-5,7-dihydro-6H-pyrrolo[3,4-d]pyrimidin-6-yl))ethan-1-one (target compound I) [ka]
[0176] Step 1: Synthesis of (R)-5-(trimethylsilyl)pentyl-4-ynyl-2-ol (5A) [ka] Trimethylsilylacetylene (51.7 g) and ethyl ether (600 mL) were added to a three-neck flask, which was cooled to -78°C under the protection of nitrogen gas. n-Butyllithium (2.5 M, 217 mL) was gradually added dropwise. After the addition was completed, the mixture was reacted for 1 hour while maintaining the temperature at -78°C. A solution of boron trifluoride in tetrahydrofuran (50%, 30 mL) was added, and (R)-propylene oxide (30 g) was gradually added dropwise. After the addition was completed, the mixture was stirred for 1 hour while maintaining the temperature. A saturated aqueous solution of sodium hydrogen carbonate (300 mL) was added to quench the reaction. After warming to room temperature, the mixture was separated, the organic phase was dried, mixed with silica gel, and purified by separation using a silica gel column (petroleum ether:ethyl acetate (V / V) = 10:1) to obtain the product, a pale yellow liquid compound (R)-5-(trimethylsilyl)pentyl-4-ynyl-2-ol (5A) (34 g, yield 42.1%).
[0177] Step 2: Synthesis of (R)-2-((5-(trimethylsilyl)pentyl-4-yn-2-yl)oxy)tert-butyl acetate (5B) [ka] The raw material (R)-5-(trimethylsilyl)pentyl-4-ynyl-2-ol (34 g, 218 mmol) was added to 340 mL of dried tetrahydrofuran, cooled to 0 ° C, 60% NaH (10.44 g, 261 mmol) was added, stirred for 30 minutes, and the raw material 2-tert-butyl bromoacetate (46.7 g, 239 mmol) was added at 0 ° C, naturally warmed to room temperature, and stirred for 16 hours. Methanol (20 mL) was added to the reaction solution at 0 ° C, mixed with silica gel, concentrated, and purified by separation using a silica gel column (petroleum ether: ethyl acetate (V / V) = 10: 1) to obtain the pale yellow liquid compound (R)-2-((5-(trimethylsilyl)pentyl-4-yn-2-yl)oxy) tert-butyl acetate (5B) (50 g, yield 85%).
[0178] Step 3: Synthesis of (R)-2-(pent-4-yn-2-yloxy) tert-butyl acetate (5C) [ka] The raw material (R)-2-((5-(trimethylsilyl)pentyl-4-yn-2-yl)oxy) tert-butyl acetate (50 g, 185 mmol) was added to 500 mL of tetrahydrofuran at room temperature, and tetrabutylammonium fluoride (53.2 g, 203 mmol) was further added and reacted at room temperature for 15 hours. Silica gel was mixed, concentrated, and the residue was separated and purified by a silica gel column (petroleum ether: ethyl acetate (V / V) = 10:1) to obtain the title yellow liquid compound, (R)-2-(pent-4-yn-2-yloxy) tert-butyl acetate (27 g, 73.7%).
[0179] Step 4: Synthesis of (R)-2-((1-(1H-1,2,3-triazol-5-yl)propan-2-yl)oxy)tert-butyl acetate (5D) [ka] The raw material (R)-2-(pent-4-yn-2-yloxy) tert-butyl acetate (27 g, 136 mmol) was added to 150 mL of DMF and 20 mL of methanol at room temperature, and azidotrimethylsilane (23.53 g, 204 mmol) and cuprous iodide (2.08 g, 10.89 mmol) were added under the protection of nitrogen gas, and the reaction solution was heated to 90 ° C and stirred for 15 hours. The reaction solution was cooled to 40 ° C, concentrated to dryness, diluted with dichloromethane, mixed with silica gel, concentrated, and the residue was purified by separation using a silica gel column (petroleum ether: ethyl acetate (V / V) = 1: 1) to obtain the yellow oily compound (R)-2-((1-(1H-1,2,3-triazol-5-yl)propan-2-yl)oxy) tert-butyl acetate (14 g, 42.6%).
[0180] Step 5: Synthesis of (R)-2-((1-(1H-1,2,3-triazol-5-yl)propan-2-yl)oxy)acetic acid (5E) [ka] The raw material (R)-2-((1-(1H-1,2,3-triazol-5-yl)propan-2-yl)oxy)tert-butyl acetate (14 g, 58 mmol) was added to a solution of hydrogen chloride in 1,4-dioxane (4 mol / L, 70 mL) at room temperature, stirred at room temperature for 16 hours, filtered, and the solid was washed with methyl tert-butyl ether and dried to obtain a white solid (R)-2-((1-(1H-1,2,3-triazol-5-yl)propan-2-yl)oxy)acetic acid (9.2 g, 86%).
[0181] Step 6: Synthesis of (R)-2-((1-(1H-1,2,3-triazol-5-yl)propan-2-yl)oxy)-1-(2-((2,3-dihydro-1H-inden-2-yl)amino)-5,7-dihydro-6H-pyrrolo[3,4-d]pyrimidin-6-yl)-ethan-1-one (target compound I) [ka] At room temperature, raw materials (R)-2-((1-(1H-1,2,3-triazol-5-yl)propan-2-yl)oxy)acetic acid (9.41 g, 42.5 mmol) and N-(2,3-dihydro-1H-inden-2-yl)-6,7-dihydro-5H-pyrrolo[3,4-d]pyrimidin-2-amine (9.2 g, 28.3 mmol) were added to 1000 mL of DMF, and T3P (50% DMF solution) (27 g, 42.5 mmol) and diisopropylethylamine (21.95 g, 170 mmol) were added at 0°C. The mixture was allowed to warm to room temperature and stirred for 16 hours. The reaction solution was filtered, water (3 mL) was added to the filtrate and concentrated to dryness. The residue was separated and purified by a silica gel column (dichloromethane:methanol (V / V) = 10:1) to obtain 12 g of crude product. The solid was slurried with 1 mL of isopropyl acetate for 10 h, filtered, and dried to give (R)-2-((1-(-1H-1,2,3-triazol-5-yl)propan-2-yl)oxy)-1-(2-((2,3-dihydro-1H-inden-2-yl)amino)-5,7-dihydro-6H-pyrrolo[3,4-d]pyrimidin-6-yl)-ethan-1-one (7.8 g, HPLC purity: 98.63%, ee value >99%, yield 65.7%).
[0182] 1 H NMR (400 MHz, DMSO-d6) δ 8.30 (d, 1H), 7.64 (b,1H), 7.57 (t, 1H), 7.22-7.20 (m, 2H), 7.16-7.12 (m, 2H), 4.65-4.59 (m, 3H), 4.52 (s, 1H), 4.42 (s, 1H), 4.25-4.17 (m, 2H), 3.87-3.81 (m, 1H), 3.27-3.21 (m, 2H), 2.90-2.85 (m, 4H), 1.19 (t, 3H). LC-MS, M / Z (ESI): 420.4(M+1).
[0183] Example 2: Preparation of salts and crystalline forms of the compound of formula (I) Approximately 15 mg of the starting compound of formula (I) as a free base and an equimolar ratio of the corresponding inorganic or organic acid were stirred in 0.5 mL of solvent at room temperature for 3 days. The clear sample was transferred to 5°C and stirred, and if no solid still precipitated, it was suspended at -20°C and stirred, and the clear sample was transferred to room temperature and evaporated. The sample was centrifuged to obtain the salt of the compound of formula (I) present in the form of a crystalline form.
[0184] The inorganic or organic acids used, the solvents and the 14 salts and 18 crystal forms obtained are shown in Table 20 below. [Table 20]
[0185] Example 3: Evaluation of the crystalline form of the salt of the compound of formula (I) Depending on the characterization results of each salt form (higher crystallinity, smaller TGA weight loss, smaller and sharper DSC endothermic peak) and the versatility and safety level of the acid, the hydrochloride salt crystalline form A, the fumarate salt crystalline form A and the benzenesulfonate salt crystalline form A were selected for the next step evaluation. Each sample prepared was characterized by XRPD, TGA, DSC, NMR or HPLC / IC, and the results are summarized in Table 21-1 below. [Table 21-1]
[0186] Hereinafter, the salt forms are evaluated using three kinds of salt forms repeatedly prepared, and the non-salt and non-solvate crystalline form A of the compound of formula (I) (also referred to as free base crystalline form A) is selected for comparison, and the evaluation items include hygroscopicity, polarized light photography (PLM), dynamic solubility and solid stability.
[0187] The 2θ diffraction angles, D values and / or relative intensities of the X-ray powder diffraction pattern of the free base crystalline form A obtained using Cu-Kα radiation are shown in Table 21-2 below. [Table 21-2]
[0188] The free base crystalline form A has an X-ray powder diffraction pattern essentially in FIG. 40, TGA and DSC curves essentially in FIG. 41, and a DVS curve essentially in FIG.
[0189] 3.1 Hygroscopicity The hygroscopicity of the hydrochloride crystal form A, the fumarate crystal form A, the benzenesulfonate crystal form A and the free base crystal form A, which were repeatedly produced, was evaluated by dynamic moisture sorption apparatus (DVS). Starting from 0% relative humidity (0% RH), the percentage mass change of the samples was collected when the humidity changed (0% RH-95% RH-0% RH) under a constant temperature condition of 25°C during the test. The DVS evaluation results are summarized in Table 21-3 below. The results show that the hydrochloride crystal form A is hygroscopic and the crystal form changes after the DVS test, while the other samples are slightly hygroscopic and no crystal transformation occurs after the DVS test. [Table 21-3]
[0190] 3.2 Polarized Light Photography (PLM) The hydrochloride salt crystalline form A, the fumarate salt crystalline form A, the benzenesulfonate salt crystalline form A and the free base crystalline form A were repeatedly prepared and characterized by polarized light microscopy (PLM). The particle size of each sample was less than 50 μm.
[0191] 3.3 Dynamic solubility The dynamic solubility of the repeatedly prepared hydrochloride, fumarate, benzenesulfonate and free base forms A in water and three biological solvents was evaluated. The dynamic solubility (1, 4 and 24 hours) of each sample in four solvent systems, water, SGF, FaSSIF and FeSSIF 1, was measured by rotary mixing (25 rpm) at 37°C with an input concentration of 5 mg / mL (20 mg of raw material was added to 4 mL of solvent). After filtering the samples at each time point by centrifugation (0.45 μm PTFE filter head), the HPLC concentration and pH value of the filtrate were measured, and the XRPD of the solid sample after centrifugation was tested. The results of the solubility test are summarized in Table 21-4 below. The results show that the solubility of the hydrochloride and benzenesulfonate forms A in each system is comparatively obviously improved compared to the free base form A. [Table 21-4]
[0192] 3.4 Solid state stability The hydrochloride crystalline form A, fumarate crystalline form A, benzenesulfonate crystalline form A and free base crystalline form A were repeatedly prepared and stored at 25℃ / 60%RH and 40℃ / 75%RH for 1 week, respectively, and then the physical and chemical stability of the samples was detected by XRPD and HPLC. The stability evaluation results are summarized in Table 21-5 below. The results show that the HPLC purity of the hydrochloride crystalline form A decreased after 1 week at 40℃ / 75%RH, and the XRPD crystallinity decreased, while the purity of the other samples did not decrease significantly after 1 week under the two conditions, and the crystal form did not change significantly. [Table 21-5]
[0193] Further testing has shown that the benzenesulfonate salt crystalline form A has excellent stability after storage for 6 months under the following conditions, with no change in any of the crystalline forms:
[0194] Condition 1: Packaging: polyethylene bag + aluminum foil bag, Inspection conditions: 40℃±2℃ / 75%RH±5%RH (the aluminum foil bag is made of an opaque material that can block light, and both the polyethylene bag and the aluminum foil bag are sealed during packaging) Condition 2: Packaging: polyethylene bag + aluminum foil bag, with desiccant filled between the outer and inner packaging. Inspection conditions: 25°C ± 2°C / 60% RH ± 10% RH (the aluminum foil bag is made of an opaque material that can block light, and both the polyethylene bag and the aluminum foil bag are sealed during packaging). Condition 3: Packaging: polyethylene bag + aluminum foil bag, with a desiccant filled between the outer and inner packaging. Inspection conditions: 2°C to 8°C (the aluminum foil bag is made of an opaque material that can block light, and both the polyethylene bag and the aluminum foil bag are sealed when packaging).
[0195] 3.5 Conclusion Three salt forms and free base crystalline form A were selected to evaluate the salt form. The DVS results show that hydrochloride crystalline form A is hygroscopic and the crystalline form changes after the DVS test, the other samples are slightly hygroscopic and no crystal transformation occurs after the DVS test. The PLM results show that the particle size of each sample is less than 50 μm. The dynamic solubility results show that the solubility of hydrochloride crystalline form A and benzenesulfonate crystalline form A in each system is significantly improved compared to free base crystalline form A. The solid stability evaluation shows that the HPLC purity of hydrochloride crystalline form A decreases after 1 week under 40℃ / 75%RH conditions, and the crystallinity of the sample decreases, while the purity of the other samples does not decrease significantly after 1 week under the two conditions, and the crystalline form does not change significantly, and the crystalline form of benzenesulfonate crystalline form A remains stable after 6 months under the above conditions.
[0196] Example 4: Evaluation of polycrystalline forms of the benzenesulfonate salt of the compound of formula (I) The benzenesulfonate crystal form A of the compound of formula (I) was used as the starting sample, and a polycrystalline form screening test was set up under a total of 100 different conditions. The screening methods included the addition of poor solvent, slow volatilization, slow cooling, suspension stirring (room temperature and 50°C), circulating heating and cooling, gas and solid penetration, gas and liquid diffusion, polymer induction and grinding. From the results of X-ray powder diffraction (XRPD) of the isolated solid, only one polycrystalline form of the benzenesulfonate salt, which was the starting crystal form A, was found. Since part of the evaluation was performed in the salt form screening stage, only the solid stability at 60°C for 24 hours was evaluated. The results are summarized in Table 22-1, and the XRPD results are shown in Figure 19, which show that the purity of the benzenesulfonate crystal form A of compound A did not obviously decrease after being placed at 60°C for 24 hours, and the crystal form did not obviously change. [Table 22-1]
[0197] The compound of formula (I) used in the following test examples is the compound of formula (I) prepared in Example 1 above, and the structure of the control compound used is as follows: [ka]
[0198] The control compound was synthesized with reference to patent application WO2014110000A1, and had an HPLC purity of 99.88%.
[0199] Test Example 1: Autotaxin (ATX) enzyme activity inhibition test The inhibitory activity of compounds against autotaxin enzyme was detected using Autotaxin Inhibitor Screening Assay Kit (Cayman, 700580). First, the compounds to be measured were prepared into 10 mM stock solution in DMSO solvent, then gradient diluted to 8 concentration points using DMSO, and then the 8 concentration points were diluted to 19× compound working solution (DMSO content is 1.9%) with Autotaxin Assay buffer (1×) provided by the reagent kit. Autotaxin Assay Reagent (10×) was taken out and diluted 10 times with Autotaxin Assay Buffer (1×). Autotaxin Substrate was taken out and dissolved by adding 1.2 mL of Autotaxin Assay Buffer (1×), mixed uniformly, and then left at room temperature. Add 150 μL of Autotaxin Assay Buffer (1×), 10 μL of diluted 19× compound working solution, 10 μL of Autotaxin Assay Reagent (1×), and 20 μL of dissolved Autotaxin Substrate to each well of the 96-well plate at each concentration point, mix evenly, shake on a shaker at a constant temperature of 37°C, and incubate in the dark for 30 min. Remove the 96-well plate and place it on a microplate reader to read the OD405. Enter the experimental results into the software GraphPad Prism, and calculate the IC of each compound by fitting. 50 was calculated. [Table 23-1]
[0200] Experimental results show that the compound of formula (I) of the present invention has excellent inhibitory activity against ATX enzyme and can effectively inhibit ATX enzyme activity.
[0201] Test Example 2: Stability test of human liver microsomes The stability test of human liver microsomes was detected by in vitro co-incubation of the compound with human liver microsomes. First, the compound to be measured was prepared in DMSO solvent to a stock solution of 10 mM, and then the compound was diluted to 0.5 mM with acetonitrile. Human liver microsomes (Corning) were diluted with PBS to a microsome / buffer solution, and the compound was diluted to 0.5 mM with the solution to a working solution, in which the concentration of the compound was 1.5 μM and the concentration of human liver microsomes was 0.75 mg / mL. A deep well plate was taken, and 30 μL of the working solution was added to each well, and then 15 μL of pre-heated 6 mM NADPH solution was added to start the reaction, and incubated at 37°C. At 0, 5, 15, 30, and 45 minutes of incubation, 135 μL of acetonitrile was added to the corresponding wells to stop the reaction. After the reaction was stopped with acetonitrile at the final 45 min, the deep-well plate was vortexed for 10 min (600 rpm / min) and then centrifuged for 15 min. After centrifugation, the supernatant was taken and purified water was added at a ratio of 1:1, followed by LC-MS / MS detection. The peak area ratio of the compound at each time point to the internal standard peak area was obtained, and the remaining percentage of the compound at each time point was calculated by comparing the peak area ratio of the compound at 5, 15, 30, and 45 min with the peak area ratio at 0 min, and the T was calculated using Excel. 1 / 2 was calculated. [Table 23-2]
[0202] Compared with the control compound, the compound of formula (I) of the present invention exhibits better liver metabolic stability, is more slowly metabolized in vivo, has higher exposure, and has a higher T of liver microsomal stability of the compound of formula (I) of the present invention. 1 / 2 is superior to the control compound, and can even reach more than twice that of the control compound, which can reduce the clinical dosage and administration frequency, reduce the toxicity and side effects of clinical administration, and improve clinical compliance.
[0203] Test Example 3: Detection of inhibitory effects of compounds on hERG using fully automated electrophysiological patch clamp QPatch The inhibitory effect of the compounds on hERG was detected by fully automated electrophysiological patch clamp QPatch. The cells used in this study were CHO cell lines (provided by Sophion Bioscience, Denmark) transfected with hERG cDNA and stably expressing hERG channels, and the cell passage number was P24. The cells were cultured in a culture medium containing the following components (all from Invitrogen): Ham's F12 medium, 10% (v / v) inactivated fetal bovine serum, 100 μg / mL hygromycin B, and 100 μg / mL Geneticin. CHO hERG cells were grown in culture dishes containing the above culture medium and cultured at 37°C in an incubator containing 5% CO2.
[0204] Extracellular solution (2 mM CaCl2, 1 mM MgCl2, 4 mM KCl, 145 mM NaCl, 10 mM glucose, 10 mM HEPES, pH approximately 7.4, osmolarity approximately 305 mOsm) and intracellular solution (5.374 mM CaCl2, 1.75 mM MgCl2, 120 mM KCl, 10 mM HEPES, 5 mM EGTA, 4 mM Na-ATP, pH approximately 7.25, osmolarity approximately 295 mOsm) were prepared.
[0205] Compounds awaiting measurement were prepared as 10 mM stock solutions in DMSO solvent, the compounds were diluted to 3, 1, 0.3, 0.1 mM in DMSO, and then the compounds were diluted to 30, 10, 3, 1, 0.3, and 0.1 μM in extracellular solution, and the final concentration of DMSO in all other compound solutions was 0.1%, except for the 30 μM compound DMSO, which had a final concentration of 0.3%.
[0206] After digestion and resuspension of the CHO hERG cells, the test was performed on an automated QPatch system (Sophion, Denmark) according to the following pre-set program:
[0207] After reaching the whole-cell configuration state with the membrane broken at the initial stage, the whole-cell current was recorded in a room temperature environment (about 25°C), and the cells were recorded for at least 120 seconds until they were stable, and the stable cells were selected for testing. In the whole test process, the cells were clamped under a voltage of -80 mV, and the cell clamp voltage was depolarized to +20 mV to activate the hERG potassium channel, and further clamped to -50 mV after 2.5 seconds to remove the inactivation and generate an outward tail current. The peak value of the tail current was used as a numerical value of the magnitude of the hERG current. The above voltage pattern was applied to the cells every 15 seconds for electrophysiological testing. An external solution containing 0.1% dimethyl sulfoxide (solvent) was added to the cells to establish a baseline, and the current was allowed to stabilize for another 3 minutes. After adding the compound solution, the cells were maintained in the test environment until the effect of the compound reached a steady state or was limited to 4 minutes. In the test experiments using various concentration gradients of the compound, the compound was added to the clamped cells from low to high concentration. After compound testing was completed, the cells were washed with external solution until the current returned to steady state.
[0208] The study data was analyzed using Qpatch analysis software provided by Sophion, Excel, and Graphpad Prism. [Table 23-3]
[0209] Compared with the control compound, the compound of formula (I) of the present invention exhibits weaker hERG inhibitory activity, and the inhibitory IC 50 In line with this value, inhibition of compounds of formula (I) exhibits a superior safety window relative to hERG, with clear advantages in cardiac safety.
[0210] Test Example 4: Thermodynamic solubility test Phosphate buffer solution (PBS) at pH 7.4, FeSSIF solution at pH 5.8 (containing 10 mM sodium taurocholate, 2 mM lecithin, 81.65 mM sodium hydroxide, 125.5 mM sodium chloride, 0.8 mM sodium oleate, 5 mM glycerol monooleate, and 55.02 mM maleic acid), and FaSSGF solution at pH 1.6 (1 L solution containing 80 μM sodium taurocholate, 20 μM lecithin, 0.1 g pepsin, and 34.2 mM sodium chloride) were prepared.
[0211] The compound was accurately weighed, and the prepared pH 7.4 phosphate buffer, pH 5.8 FeSSIF solution, and pH 1.6 FaSSGF solution were added to prepare a solution with a concentration of 4 mg / mL. The solution was shaken at a rotation speed of 1000 rpm for 1 hour and then incubated at room temperature overnight. The incubated solution was centrifuged at a rotation speed of 12000 rpm for 10 minutes to remove undissolved particles, and the supernatant was transferred to a new centrifuge tube. After the supernatant was appropriately diluted, an acetonitrile solution containing an internal standard was added and quantified with a standard curve prepared with the same substrate. [Table 23-4]
[0212] Experimental results show that the solubility of the control compound is relatively low, and the absorption in the gastrointestinal tract is relatively low, which is not useful for the development of oral drugs.Compared with the control compound, the compound of formula (I) of the present invention has significantly improved thermodynamic solubility under simulated gastric fluid, simulated intestinal fluid and neutral conditions, and is therefore expected to greatly improve intestinal absorption in the body, have a relatively high oral exposure, reduce clinical dosage, and improve clinical compliance.
[0213] Test Example 5: Pharmacokinetics test In the in vivo pharmacokinetic study in rats, six male SD rats weighing 180-240 g were used and fasted overnight. Three rats were given 10 mg / kg by oral gavage, and blood samples were taken before and 15, 30 minutes, and 1, 2, 4, 8, and 24 hours after administration. Another three rats were given 1 mg / kg by intravenous injection, and blood samples were taken before and 5, 15, 30 minutes, and 1, 2, 4, 8, and 24 hours after administration. The blood samples were centrifuged at 8000 rpm at 4°C for 6 minutes, and plasma was collected and stored at -20°C. Three to five volumes of acetonitrile solution containing the internal standard were added to the plasma at each time point, mixed, vortexed for 1 minute, centrifuged at 13000 rpm at 4°C for 10 minutes, and the supernatant was added with three volumes of water and mixed. An appropriate amount of the mixture was taken for LC-MS / MS analysis. The main pharmacokinetic parameters were analyzed by non-compartmental modeling using WinNonlin 7.0 software.
[0214] For the in vivo pharmacokinetic study in mice, 18 male ICR mice weighing 20–25 g were used and fasted overnight. Nine mice were given 10 mg / kg by gavage, and blood was collected alternately from three mice at each blood collection time point, for a total of nine mice. Another nine mice were given 1 mg / kg by intravenous injection, and blood was collected alternately from three mice at each blood collection time point, for a total of nine mice. The remaining procedures were the same as those for the rat pharmacokinetic study. [Table 23-5] [Table 23-6]
[0215] The experimental results show that the compound of formula (I) of the present invention has better pharmacokinetic properties than the control compound. In particular, in rats, the clearance rate (CL) of the compound of formula (I) of the present invention is lower, about 1 / 6 of that of the control compound, indicating that the compound of formula (I) is relatively stable in the body, and the C max and AUC 0-t It can reach 6.1 and 4.2 times that of the control compound, respectively.
[0216] Test Example 6: Inhibition test for ATX enzyme activity in human plasma Whole blood was collected from healthy volunteers and anticoagulated with heparin, the blood collection tubes were centrifuged at 3000 rpm for 10 min, and the plasma was stored at −80°C until ready for use.
[0217] The compounds were serially diluted with DMSO according to the conventional concentration requirements, then 3 μL was added to a 96-well plate, 147 μL of PBS was taken and added to the wells containing 3 μL of compound, and 50 μL was taken and added to a new 96-well plate after uniform mixing. Human plasma was taken out of the -80°C refrigerator and thawed by rapid shaking in a 37°C water bath, and 50 μL of human plasma was added to the 96-well plate containing 50 μL of diluted compound (the final system is 1% DMSO). The group without compound was set as the positive group. The 96-well plate was shaken to mix uniformly and incubated at 37°C for 3 hours. Another blank group was set, and the plasma of the blank group was stored at -80°C, and the action of the blank group was to measure the baseline concentration of endogenous LPA.
[0218] After the incubation was completed, the blank group was thawed on ice and transferred to an incubation plate. An excess of acetonitrile containing the internal standard LPA17:0 was added to the incubation plate to precipitate plasma proteins. After centrifugation by vortexing, the supernatant was removed and diluted, and the peak areas of LPA18:2 and the internal standard LPA17:0 were detected by LC-MSMS mass spectrometry.
[0219] The peak area ratio between LPA18:2 and the internal standard LPA17:0 was calculated, and the inhibition rate of LPA18:2 production was calculated according to the following formula.
[0220] Inhibition rate (%) = 100-(various concentrations of compounds-blank group) / (positive group-blank group)*100 Based on the inhibition rate at various concentrations of the compound, the inhibitory IC of the compound against ATX enzyme activity in human plasma was calculated. 50 values were calculated. [Table 23-7]
[0221] The experimental results show that the compound of formula (I) of the present invention has very good inhibitory activity against ATX enzyme in human plasma, can effectively inhibit ATX enzyme activity, and is obviously superior to the control compound.
[0222] Test Example 7: Rat bleomycin-induced IPF model A bleomycin-induced IPF model (idiopathic pulmonary fibrosis model) was performed using male BN rats weighing 180-240 g at a dose of 5 U / kg. After modeling, the animals were randomly divided into a solvent control group, a GLPG-1690 group (a clinical phase III compound from Galapagos), a control compound group, and a compound of formula (I), and were orally administered twice a day from the second day after modeling, with the treatment group receiving 30 mg / kg per dose, and the solvent control group receiving blank solvent, for 21 consecutive days.
[0223] During the administration period, body weight was measured every 3 days. On the 21st day of administration, 2 h after the first administration, alveolar lavage was performed, inflammatory cells in the lavage fluid were counted, and related biomarkers were detected in the lavage fluid supernatant. After lavage, the left lung of the rat was taken and fixed, Masson's trichrome staining was used for pathological scoring of fibrosis, and the remaining lung lobe was frozen and preserved. The alveolar lavage fluid supernatant and freshly frozen lung tissue of the compound 3 group were collected, and the TGF-β1 protein content and total protein amount were detected by ELISA, and the amount of TGF-β1 per mg of total protein was calculated.
[0224] The experimental results showed that the compound of formula (I) significantly reduced animal body weight compared to the control compound group, and the safety of the compound of formula (1) was superior (results are shown in Figure 43); the TGF-β1 content in the bronchoalveolar lavage supernatant and freshly frozen lung tissue of the compound of formula (I) was significantly lower than that of the solvent control group, and the compound of formula (I) had a significant anti-fibrotic effect (results are shown in Figure 44).
[0225] Test Example 8: Pharmacokinetic study (crystalline form) In the in vivo pharmacokinetic study in mice, nine male ICR mice weighing 20-25 g were used, fasted overnight, and administered 10 mg / kg orally by force. Three mice were collected at each blood collection time point, for a total of nine mice, and blood was collected alternately at 15 and 30 minutes before and after administration, and at 1, 2, 4, 8, 12, and 24 hours. The blood samples were centrifuged at 8000 rpm for 6 minutes at 4°C, and the plasma was collected and stored at -20°C. Three to five volumes of acetonitrile solution containing an internal standard were added to the plasma at each time point, mixed, vortexed for 1 minute, centrifuged at 13000 rpm for 10 minutes at 4°C, and the supernatant was added with three volumes of water and mixed. An appropriate amount of the mixture was taken for LC-MS / MS analysis. The main pharmacokinetic parameters were analyzed by a non-compartmental model using WinNonlin 7.0 software. [Table 23-8]
[0226] The experimental results show that, compared with the control compound, the benzenesulfonate crystalline form A of compound of formula (I) of the present invention has more excellent pharmacokinetic properties.
[0227] The above describes the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modifications, equivalent replacements, improvements, etc. made within the scope of the present invention without departing from the spirit and principles of the present invention should be included within the scope of the claims of the present invention.
Claims
1. A salt of a compound of formula (I), 【Chemistry 1】 A salt of a compound of formula (I), wherein the salt is selected from an inorganic acid salt or an organic acid salt.
2. The salt of the compound of formula (I) according to claim 1, wherein the inorganic or organic acid which forms a salt with the compound of formula (I) is one or more selected from hydrochloric acid, sulfuric acid, phosphoric acid, hydrobromic acid, aspartic acid, maleic acid, glutamic acid, mucic acid, tartaric acid, fumaric acid, citric acid, glycolic acid, malic acid, hippuric acid, lactic acid, ascorbic acid, succinic acid, adipic acid, sebacic acid, lauric acid, p-toluenesulfonic acid, methanesulfonic acid, benzenesulfonic acid, benzoic acid, and niacin.
3. The hydrochloride crystalline A of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of the hydrochloride crystalline A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 7.48±0.20°, 13.13±0.20°, 16.47±0.20°, and 23.94±0.20°.
4. The hydrochloride salt crystalline A of the compound of formula (I) according to claim 3, wherein the X-ray powder diffraction pattern of the hydrochloride salt crystalline A has characteristic peaks at 2θ angles of 7.48±0.20°, 13.13±0.20°, 16.47±0.20°, 18.29±0.20°, 19.89±0.20°, and 23.94±0.20°.
5. The hydrochloride salt crystalline A of the compound of formula (I) according to claim 3, wherein the X-ray powder diffraction pattern of the hydrochloride salt crystalline A has characteristic peaks at 2θ angles of 7.48±0.20°, 13.13±0.20°, 14.86±0.20°, 16.47±0.20°, 18.29±0.20°, 19.89±0.20°, 23.94±0.20°, and 26.92±0.20°.
6. The hydrochloride salt crystalline A has one, two, three or four of the following characteristics: (1) The TGA curve of hydrochloride crystalline A shows a weight loss of 2.83% at 150.0±3℃; (2) The DSC curve of hydrochloride crystalline A has an endothermic peak at 163.5±3°C; (3) The DSC curve of hydrochloride crystalline A has an endothermic peak at 170.9±10°C; (4) The DVS curve of hydrochloride crystalline A shows that the water adsorption is less than 3.85% under conditions of 0% RH to 80% RH. A crystalline hydrochloride salt A of the compound of formula (I) according to any one of claims 3 to 5.
7. The sulfate crystalline salt A of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of the sulfate crystalline salt A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.49±0.20°, 15.88±0.20°, 17.48±0.20°, and 22.40±0.20°.
8. The sulfate crystalline A of the compound of formula (I) according to claim 7, wherein the X-ray powder diffraction pattern of the sulfate crystalline A has characteristic peaks at 2θ angles of 5.49±0.20°, 6.93±0.20°, 11.08±0.20°, 15.88±0.20°, 17.48±0.20°, 20.82±0.20°, and 22.40±0.20°.
9. The sulfate crystal A has one, two or three of the following characteristics: (1) The TGA curve of sulfate crystal A shows a weight loss of 3.53% at 150.0±3℃; (2) The DSC curve of sulfate crystal A has an endothermic peak at 131.8±3°C; (3) The DSC curve of sulfate crystal A has an endothermic peak at 141.9±5°C; A crystalline sulfate salt A of the compound of formula (I) according to claim 7 or 8.
10. The maleate crystalline A of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of the maleate crystalline A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 4.43±0.20°, 13.86±0.20°, 14.41±0.20°, 15.00±0.20°, 22.07±0.20°, 22.65±0.20°, 25.58±0.20°, and 27.34±0.20°.
11. The maleate crystalline A of the compound of formula (I) according to claim 10, wherein the X-ray powder diffraction pattern of the maleate crystalline A has characteristic peaks at 2θ angles of 4.43±0.20°, 9.92±0.20°, 13.86±0.20°, 14.41±0.20°, 15.00±0.20°, 17.82±0.20°, 22.07±0.20°, 22.65±0.20°, 25.58±0.20°, and 27.34±0.20°.
12. The maleate crystalline A of the compound of formula (I) according to claim 10, wherein the X-ray powder diffraction pattern of the maleate crystalline A has characteristic peaks at 2θ angles of 4.43±0.20°, 9.92±0.20°, 13.86±0.20°, 14.41±0.20°, 15.00±0.20°, 17.82±0.20°, 22.07±0.20°, 22.65±0.20°, 24.20±0.20°, 24.53±0.20°, 25.58±0.20°, 25.84±0.20°, and 27.34±0.20°.
13. The maleate crystalline salt A has one or two of the following characteristics: (1) The TGA curve of maleate crystal A shows a weight loss of 10.48% at 150.0±3℃; (2) The DSC curve of maleate crystal A has two endothermic peaks at 103.0±5°C and 132.8±5°C; A crystalline maleate salt A of the compound of formula (I) according to any one of claims 10 to 12.
14. Phosphate crystalline A of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of said phosphate crystalline A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.08±0.20°, 15.93±0.20°, 24.37±0.20°, and 25.19±0.20°.
15. The phosphate crystal A has one or two of the following characteristics: (1) The TGA curve of phosphate crystal A shows a weight loss of 12.68% at 150.0±3℃; (2) The DSC curve of phosphate crystal A has two endothermic peaks at 89.4±3°C and 94.3±3°C; A crystalline phosphate salt A of the compound of formula (I) according to claim 14.
16. Tartrate crystal A, Tartrate crystal B or Tartrate crystal C, which are as follows: The X-ray powder diffraction pattern of the tartrate salt crystal A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.00±0.20° and 15.88±0.20°, The X-ray powder diffraction pattern of the tartrate salt crystal B obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.24±0.20° and 23.94±0.20°; and The X-ray powder diffraction pattern of the tartrate salt crystalline C obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 4.60±0.20°, 16.15±0.20°, and 18.13±0.20°. The tartrate salt crystalline A, tartrate salt crystalline B or tartrate salt crystalline C of the compound of formula (I) according to claim 1.
17. the X-ray powder diffraction pattern of the Tartrate Salt Crystalline A has characteristic peaks at 2θ angles of 5.00±0.20°, 7.34±0.20°, 8.59±0.20°, 15.88±0.20°, 19.54±0.20°, 21.46±0.20°, 23.43±0.20°, and 25.08±0.20°; or The X-ray powder diffraction pattern of the Tartrate Salt Crystalline C has characteristic peaks at 2θ angles of 4.60±0.20°, 7.58±0.20°, 14.39±0.20°, 16.15±0.20°, 18.13±0.20°, 22.32±0.20°, 24.44±0.20°, and 26.69±0.20°; The crystalline tartrate salt A, crystalline tartrate salt B or crystalline tartrate salt C of the compound of formula (I) according to claim 16.
18. A crystalline tartrate salt A, crystalline tartrate salt B or crystalline tartrate salt C of the compound of formula (I) according to claim 16 or 17, The tartrate salt crystalline A has one or two of the following characteristics: (1) The TGA curve of tartrate salt crystal A shows a weight loss of 14.67% at 150.0±3℃; (2) The DSC curve of tartrate salt crystal A has an endothermic peak at 96.8±5°C; or The Tartrate Crystal B has one, two or three of the following characteristics: (1) The TGA curve of tartrate salt crystal B shows a weight loss of 4.87% at 150.0±3℃; (2) The DSC curve of tartrate salt crystal B has an endothermic peak onset at 173.9±3°C; (3) The DSC curve of tartrate salt crystal B has an endothermic peak at 175.3±3°C; 18. Crystalline tartrate salt A, crystalline tartrate salt B or crystalline tartrate salt C of the compound of formula (I) according to claim 16 or 17.
19. The fumarate salt crystalline A of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of the fumarate salt crystalline A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 9.52±0.20°, 13.29±0.20°, 14.92±0.20°, and 25.23±0.20°.
20. 20. The compound of formula (I) according to claim 19, wherein the X-ray powder diffraction pattern of said crystalline fumarate A has characteristic peaks at 2θ angles of 9.52±0.20°, 13.29±0.20°, 14.92±0.20°, 19.02±0.20°, 21.39±0.20°, 25.23±0.20°, and 28.07±0.20°.
21. The Fumarate Crystalline A has one, two, three or four of the following characteristics: (1) The TGA curve of fumarate crystalline A shows a weight loss of 3.86% at 150.0±3℃; (2) The DSC curve of fumarate crystalline A has an endothermic peak at 208.6±3°C; (3) The DSC curve of fumarate salt crystalline A has an endothermic peak at 210.2±3°C; (4) The DVS curve of fumarate crystal A shows that the moisture adsorption is less than 0.60% under the conditions of 0% RH to 85% RH; A crystalline fumarate salt A of the compound of formula (I) according to claim 19 or 20.
22. The citrate crystalline A of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of the citrate crystalline A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 4.96±0.20° and 15.76±0.20°.
23. The Citrate Crystal A has one or two of the following characteristics: (1) The TGA curve of citrate salt crystal A shows a weight loss of 10.24% at 150.0±3℃; (2) The DSC curve of citrate salt crystal A has an endothermic peak at 91.2±3°C; A crystalline citrate salt A of the compound of formula (I) according to claim 22.
24. The glycolate salt crystalline A of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of the glycolate salt crystalline A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.26±0.20°, 7.27±0.20°, 14.12±0.20°, 16.02±0.20°, and 24.11±0.20°.
25. The glycolate crystalline salt A has one or two of the following characteristics: (1) The TGA curve of glycolate crystal A shows a weight loss of 7.72% at 150.0±3℃; (2) The DSC curve of glycolate crystal A has an endothermic peak at 103.1±10°C; A crystalline glycolate salt A of the compound of formula (I) according to claim 24.
26. Succinate crystal A or succinate crystal B, The X-ray powder diffraction pattern of the succinate crystalline salt A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 5.26±0.20°, 14.00±0.20°, 15.76±0.20°, 21.07±0.20°, 22.00±0.20°, and 27.08±0.20°; The X-ray powder diffraction pattern of the succinate crystalline salt B obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 9.54±0.20°, 12.60±0.20°, 14.91±0.20°, 19.17±0.20°, 21.02±0.20°, and 24.88±0.20°. A crystalline succinate A or a crystalline succinate B of the compound of formula (I) according to claim 1.
27. A crystalline succinate A or a crystalline succinate B of the compound of formula (I) according to claim 26, the X-ray powder diffraction pattern of the succinate salt crystalline A has characteristic peaks at 2θ angles of 5.26±0.20°, 6.99±0.20°, 7.35±0.20°, 14.00±0.20°, 15.76±0.20°, 21.07±0.20°, 22.00±0.20°, and 27.08±0.20°; or The X-ray powder diffraction pattern of the succinate salt crystalline B has characteristic peaks at 2θ angles of 9.54±0.20°, 12.60±0.20°, 13.28±0.20°, 14.91±0.20°, 15.20±0.20°, 19.17±0.20°, 21.02±0.20°, 24.88±0.20°, and 28.15±0.20°. A crystalline succinate A or a crystalline succinate B of the compound of formula (I) according to claim 26.
28. 27. The succinate crystalline salt A or succinate crystalline salt B of the compound of formula (I) according to claim 26, wherein the X-ray powder diffraction pattern of the succinate crystalline salt B has characteristic peaks at 2θ angles of 9.54±0.20°, 12.60±0.20°, 13.28±0.20°, 14.91±0.20°, 15.20±0.20°, 19.17±0.20°, 19.77±0.20°, 21.02±0.20°, 21.44±0.20°, 24.88±0.20°, 25.22±0.20°, and 28.15±0.20°.
29. A crystalline succinate A or a crystalline succinate B of the compound of formula (I) according to any one of claims 26 to 28, The succinate crystalline salt A has one or two of the following characteristics: (1) The TGA curve of succinate crystal A shows a weight loss of 3.74% at 150.0±3℃; (2) The DSC curve of the succinate salt crystalline A has four endothermic peaks at 73.3±5°C, 102.2±5°C, 136.6±5°C and 173.6±5°C; or The succinate salt crystalline B has one, two or three of the following characteristics: (1) The TGA curve of succinate crystalline B shows a weight loss of 0.83% at 150.0±3℃; (2) The DSC curve of succinate crystal B has an endothermic peak at 128.8±3°C; (3) The DSC curve of succinate crystal B has an endothermic peak at 129.9±3°C; A crystalline succinate A or a crystalline succinate B of the compound of formula (I) according to any one of claims 26 to 28.
30. The adipate crystalline B of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of the adipate crystalline B obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 4.98±0.20°, 10.69±0.20°, 13.88±0.20°, 21.41±0.20°, 24.97±0.20°, and 26.15±0.20°.
31. 31. The adipate salt crystalline B of the compound of formula (I) according to claim 30, wherein the X-ray powder diffraction pattern of the adipate salt crystalline B has characteristic peaks at 2θ angles of 4.98±0.20°, 10.69±0.20°, 13.88±0.20°, 14.28±0.20°, 20.72±0.20°, 21.41±0.20°, 24.97±0.20°, and 26.15±0.20°.
32. 31. The adipate salt crystalline B of the compound of formula (I) according to claim 30, wherein the X-ray powder diffraction pattern of the adipate salt crystalline B has characteristic peaks at 2θ angles of 4.98±0.20°, 9.23±0.20°, 10.69±0.20°, 13.88±0.20°, 14.28±0.20°, 19.35±0.20°, 20.72±0.20°, 21.41±0.20°, 24.97±0.20°, and 26.15±0.20°.
33. The adipate crystalline B has one, two or three of the following characteristics: (1) The TGA curve of adipate crystal B shows a weight loss of 1.23% at 150.0±3℃; (2) The DSC curve of adipate crystal B has an endothermic peak at 112.8±3°C; (3) The DSC curve of adipate crystal B has an endothermic peak at 115.6±3°C; A crystalline form of the adipate salt B of the compound of formula (I) according to any one of claims 30 to 32.
34. The crystalline sebacate A of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of the crystalline sebacate A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 4.57±0.20°, 9.27±0.20°, 11.20±0.20°, 14.40±0.20°, 20.16±0.20°, 24.63±0.20°, and 26.73±0.20°.
35. The crystalline sebacate A of the compound of formula (I) according to claim 34, wherein the X-ray powder diffraction pattern of the crystalline sebacate A has characteristic peaks at 2θ angles of 4.57±0.20°, 9.27±0.20°, 11.20±0.20°, 14.40±0.20°, 14.95±0.20°, 20.16±0.20°, 20.55±0.20°, 22.95±0.20°, 23.91±0.20°, 24.63±0.20°, and 26.73±0.20°.
36. 35. The crystalline sebacate salt A of the compound of formula (I) according to claim 34, wherein the X-ray powder diffraction pattern of the crystalline sebacate salt A has characteristic peaks at 2θ angles of 4.57±0.20°, 9.27±0.20°, 11.20±0.20°, 14.40±0.20°, 14.95±0.20°, 15.26±0.20°, 18.25±0.20°, 20.16±0.20°, 20.95±0.20°, 22.95±0.20°, 23.91±0.20°, 24.63±0.20°, and 26.73±0.20°.
37. The crystalline sebacate A has one or two of the following characteristics: (1) The TGA curve of crystalline sebacate A shows a weight loss of 0.45% at 150.0±3℃; (2) The DSC curve of crystalline sebacate A has two endothermic peaks at 80.9±10°C and 142.1±10°C; A crystalline sebacate salt A of the compound of formula (I) according to any one of claims 34 to 36.
38. 2. The p-toluenesulfonate crystalline A of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of the p-toluenesulfonate crystalline A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 6.04±0.20°, 8.59±0.20°, 14.27±0.20°, 17.14±0.20°, and 25.29±0.20°.
39. 39. The p-toluenesulfonate crystalline A of the compound of formula (I) according to claim 38, wherein the X-ray powder diffraction pattern of the p-toluenesulfonate crystalline A has characteristic peaks at 2θ angles of 6.04±0.20°, 8.59±0.20°, 14.27±0.20°, 17.14±0.20°, 20.41±0.20°, 23.68±0.20°, 25.29±0.20°, and 27.65±0.20°.
40. 39. The p-toluenesulfonate crystalline A of the compound of formula (I) according to claim 38, wherein the X-ray powder diffraction pattern of the p-toluenesulfonate crystalline A has characteristic peaks at 2θ angles of 6.04±0.20°, 8.59±0.20°, 12.28±0.20°, 14.27±0.20°, 16.02±0.20°, 17.14±0.20°, 20.41±0.20°, 22.01±0.20°, 23.68±0.20°, 25.29±0.20°, and 27.65±0.20°.
41. The p-toluenesulfonate crystalline salt A has one or two of the following characteristics: (1) The TGA curve of p-toluenesulfonate crystalline A shows a weight loss of 3.29% at 150.0±3°C; (2) The DSC curve of p-toluenesulfonate crystalline A has an endothermic peak at 210.8±5°C; A crystalline p-toluenesulfonate salt A of the compound of formula (I) according to any one of claims 38 to 40.
42. The benzenesulfonate crystalline A of the compound of formula (I) according to claim 1, wherein the X-ray powder diffraction pattern of the benzenesulfonate crystalline A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 6.16±0.20°, 8.98±0.20°, 14.22±0.20°, 16.90±0.20°, 18.31±0.20°, 20.92±0.20°, 25.11±0.20°, and 26.29±0.20°.
43. The benzenesulfonate crystalline A of the compound of formula (I) according to claim 42, wherein the X-ray powder diffraction pattern of the benzenesulfonate crystalline A has characteristic peaks at 2θ angles of 6.16±0.20°, 8.98±0.20°, 14.22±0.20°, 15.67±0.20°, 16.90±0.20°, 17.55±0.20°, 18.31±0.20°, 20.34±0.20°, 20.92±0.20°, 25.11±0.20°, 26.29±0.20°, and 29.24±0.20°.
44. The benzenesulfonate crystalline A of the compound of formula (I) according to claim 42, wherein the X-ray powder diffraction pattern of the benzenesulfonate crystalline A has characteristic peaks at 2θ angles of 6.16±0.20°, 8.98±0.20°, 14.22±0.20°, 15.67±0.20°, 16.90±0.20°, 17.55±0.20°, 18.31±0.20°, 20.34±0.20°, 20.92±0.20°, 23.54±0.20°, 24.65±0.20°, 25.11±0.20°, 26.29±0.20°, and 29.24±0.20°.
45. The benzenesulfonate salt crystalline A has one, two, three or four of the following characteristics: (1) The TGA curve of benzenesulfonate crystal A shows a weight loss of 1.87% at 150.0±3℃; (2) The DSC curve of benzenesulfonate crystal A has an endothermic peak at 184.7±3°C; (3) The DSC curve of benzenesulfonate crystal A has an endothermic peak at 187.0±3°C; (4) The DVS curve of benzenesulfonate crystal A shows that the moisture adsorption is less than 1.46% under the conditions of 0% RH to 85% RH; A crystalline benzenesulfonate salt A of the compound of formula (I) according to any one of claims 42 to 44.
46. Hydrobromide crystal A or hydrobromide crystal B, The X-ray powder diffraction pattern of the hydrobromide salt crystalline A obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 9.54±0.20° and 24.63±0.20°; The X-ray powder diffraction pattern of the hydrobromide salt crystalline B obtained using Cu-Kα radiation has characteristic peaks at 2θ angles of 9.48±0.20°, 15.89±0.20°, and 23.98±0.20°. A crystalline hydrobromide salt A or a crystalline hydrobromide salt B of the compound of formula (I) according to claim 1.
47. 47. The hydrobromide salt crystalline A or hydrobromide salt crystalline B of the compound of formula (I) according to claim 46, wherein the X-ray powder diffraction pattern of the hydrobromide salt crystalline B has characteristic peaks at 2θ angles of 9.48±0.20°, 15.89±0.20°, 19.40±0.20°, 23.98±0.20°, 26.55±0.20°, and 28.02±0.20°.
48. A crystalline hydrobromide salt A or a crystalline hydrobromide salt B of the compound of formula (I) according to any one of claims 46 and 47, The hydrobromide salt crystalline A has one or two of the following characteristics: (1) The TGA curve of hydrobromide salt crystalline A shows a weight loss of 7.86% at 150.0±3℃; (2) The DSC curve for Hydrobromide Crystal A has three endothermic peaks at 96.5±5°C, 107.3±5°C, and 141.8±5°C; or The hydrobromide salt crystalline B has one or two of the following characteristics: (1) The TGA curve of hydrobromide salt crystalline B shows a weight loss of 4.95% at 150.0±3℃; (2) The DSC curve of hydrobromide salt crystalline B has three endothermic peaks at 81.6±5°C, 128.9±5°C, and 163.6±5°C; 48. A crystalline hydrobromide salt A or a crystalline hydrobromide salt B of the compound of formula (I) according to any one of claims 46 or 47.
49. A pharmaceutical composition comprising: A salt of a compound of formula (I) according to any one of claims 1 to 2; A crystalline hydrochloride salt A of the compound of formula (I) according to any one of claims 3 to 6; A crystalline sulfate salt A of the compound of formula (I) according to any one of claims 7 to 9; A crystalline maleate salt A of the compound of formula (I) according to any one of claims 10 to 13; A crystalline phosphate salt A of the compound of formula (I) according to claim 14 or 15; A crystalline tartrate salt A, crystalline tartrate salt B or crystalline tartrate salt C of the compound of formula (I) according to any one of claims 16 to 18; A crystalline fumarate salt A of the compound of formula (I) according to any one of claims 19 to 21; A crystalline citrate salt A of the compound of formula (I) according to claim 22 or 23; A crystalline glycolate salt of the compound of formula (I) according to claim 24 or 25; A crystalline succinate A or a crystalline succinate B of the compound of formula (I) according to any one of claims 26 to 29; A crystalline form of the adipate salt of the compound of formula (I) according to any one of claims 30 to 33; A crystalline sebacate salt A of the compound of formula (I) according to any one of claims 34 to 37; A crystalline p-toluenesulfonate salt A of the compound of formula (I) according to any one of claims 38 to 41; A crystalline benzenesulfonate salt A of the compound of formula (I) according to any one of claims 42 to 45; A crystalline hydrobromide salt A or a crystalline hydrobromide salt B of the compound of formula (I) according to any one of claims 46 to 48; or A mixture of any two or more of these.
50. Use of the following in the manufacture of a medicament for treating and / or preventing an autotaxin ATX-related disease: A salt of a compound of formula (I) according to any one of claims 1 to 2; A crystalline hydrochloride salt A of the compound of formula (I) according to any one of claims 3 to 6; A crystalline sulfate salt A of the compound of formula (I) according to any one of claims 7 to 9; A crystalline maleate salt A of the compound of formula (I) according to any one of claims 10 to 13; A crystalline phosphate salt A of the compound of formula (I) according to claim 14 or 15; A crystalline tartrate salt A, crystalline tartrate salt B or crystalline tartrate salt C of the compound of formula (I) according to any one of claims 16 to 18; A crystalline fumarate salt A of the compound of formula (I) according to any one of claims 19 to 21; A crystalline citrate salt A of the compound of formula (I) according to claim 22 or 23; A crystalline glycolate salt of the compound of formula (I) according to claim 24 or 25; A crystalline succinate A or a crystalline succinate B of the compound of formula (I) according to any one of claims 26 to 29; A crystalline form of the adipate salt of the compound of formula (I) according to any one of claims 30 to 33; A crystalline sebacate salt A of the compound of formula (I) according to any one of claims 34 to 37; A crystalline p-toluenesulfonate salt A of the compound of formula (I) according to any one of claims 38 to 41; A crystalline benzenesulfonate salt A of the compound of formula (I) according to any one of claims 42 to 45; A crystalline hydrobromide salt A or a crystalline hydrobromide salt B of the compound of formula (I) according to any one of claims 46 to 48; or A mixture of any two or more of these.
51. The use according to claim 50, wherein the ATX-related disease comprises at least one selected from cancer, metabolic disease, kidney disease, liver disease, fibrodegenerative disease, interstitial lung disease, proliferative disease, inflammatory disease, pain, autoimmune disease, respiratory disease, cardiovascular disease, neurodegenerative disease, dermatological disorder and / or disease associated with abnormal angiogenesis.
52. The use according to claim 50, wherein the ATX-associated disease comprises at least one selected from interstitial lung disease, pulmonary fibrosis, liver fibrosis, and renal fibrosis.
53. 51. The use of claim 50, wherein the ATX-related disease includes idiopathic pulmonary fibrosis, type 2 diabetes, non-alcoholic steatohepatitis, neuropathic pain, and inflammatory pain.
54. 51. The use of claim 50, wherein the ATX-associated disease comprises pain associated with osteoarthritis.
Citation Information
Patent Citations
bicyclic pyrimidine compounds
JP2016505010A
imidazopyridine compound
JP2016512254A
Pyrrolopyrimidine derivative and use thereof
WO2020156459A1